Resin layer, optical film and image display device
The resin layer with varying hardness levels in the thickness direction addresses foldability and impact resistance issues in optical films for foldable image display devices, enhancing durability and visibility.
Patent Information
- Application Number
- JP2024047166
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-27
- Filing Date
- 2024-03-22
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2040-02-27
AI Technical Summary
Foldable image display devices require optical films with good foldability, impact resistance, and resistance to pressure marks, while minimizing creases and breaks, as existing solutions often compromise on these properties.
A resin layer with specific displacement amounts in its thickness direction, forming three regions with varying hardness levels (d1 < d2 < d3), integrated into an optical film with a functional layer and a resin base material, ensuring balanced foldability and impact resistance.
The solution provides an optical film that is less prone to creasing, pressure marks, and breaks, while maintaining good impact resistance, suitable for use in foldable image display devices.
Smart Images

Figure 0007619504000033 
Figure 0007619504000034 
Figure 0007619504000035
Abstract
Description
REFERENCE TO RELATED APPLICATIONS
[0001] This application claims the benefit of priority from earlier Japanese applications No. 2019-37342 (filed March 1, 2019), No. 2019-68027 (filed March 29, 2019), and No. 2019-177178 (filed September 27, 2019), the entire disclosures of which are incorporated herein by reference. [Technical field]
[0002] The present invention relates to a resin layer, an optical film, and an image display device. [Background technology]
[0003] Conventionally, image display devices such as smartphones and tablet terminals have been known, but currently, foldable image display devices are being developed. Usually, smartphones and tablet terminals are covered with a cover glass. Glass is generally excellent in hardness but is difficult to bend, so if a cover glass is used for an image display device, there is a high possibility that the image display device will break when folded. For this reason, instead of a cover glass, it is being considered to use a foldable optical film having a bendable resin substrate and a hard coat layer or a foldable optical film made of resin for a foldable image display device (see, for example, Patent Documents 1 and 2). Patent Document 2 discloses that organic particles are contained in the hard coat layer to suppress external light reflection and glare. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-125063 A [Patent Document 2] International Publication No. 2017 / 14198 Summary of the Invention [Problem to be solved by the invention]
[0005] In the optical film used in such a foldable image display device, good foldability is required, and impact resistance is also required because an impact may be applied to the surface of the optical film. Here, if an impact is applied from the surface side of the optical film, the surface of the optical film may be dented and a member (e.g., a polarizing plate) located inside the optical film in the image display device may be damaged. For this reason, impact resistance is required such that the surface of the optical film is not dented when an impact is applied to the surface of the optical film, or impact resistance is required such that the surface of the optical film is not dented when an impact is applied to the surface of the optical film and a member (e.g., a polarizing plate) located inside the optical film in the image display device is not damaged when an impact is applied to the surface of the optical film.
[0006] In addition, when such an optical film is held in a folded state, a fold may be formed at the bent portion of the optical film. Although optical films having good foldability have been proposed so far, no consideration has been given to the fold. Here, the foldability is an index that evaluates cracking or breakage when folded, and is therefore completely different from the absence of a fold. For this reason, even an optical film having good foldability may develop a fold.
[0007] In addition, since the foldable optical film is used in place of a cover glass, it may be pressed by a finger. However, since it is softer than the cover glass, it may be temporarily indented and leave a mark (pressure mark).
[0008] Currently, the addition of organic particles to the hard coat layer is being considered in order to make pressure marks less noticeable; however, adding organic particles raises the risk of cracks forming at the interface between the organic particles and the binder resin when the film is folded, causing the optical film to break.
[0009] The present invention has been made to solve the above problems. That is, an object of the present invention is to provide a resin layer having good foldability and good impact resistance, an optical film including the same, and an image display device. Another object of the present invention is to provide a foldable optical film that is difficult to develop folds and has good impact resistance, and an image display device including the same. Still another object of the present invention is to provide a foldable optical film in which pressing marks are difficult to be noticeable and that is difficult to crack during folding, and an image display device including the same.
Means for Solving the Problems
[0010] The present invention includes the following inventions. [1] A resin layer used in an image display device and having light transmissibility, wherein the resin layer is divided into three equal parts in the film thickness direction of the resin layer, and is sequentially defined as a first region, a second region, and a third region from a first surface of the resin layer toward a second surface opposite to the first surface. When an indentation test is performed by pressing a Berkovich indenter into the first region, the second region, and the third region of the resin layer in the cross section of the resin layer in the film thickness direction with a constant load, and the displacement amount in the first region is d1, the displacement amount in the second region is d2, and the displacement amount in the third region is d3, a resin layer satisfying the relationship d1 < d2 < d3.
[0011] [2] The resin layer according to [1] above, wherein the ratio of the displacement amount d1 to the displacement amount d3 is 0.85 or less.
[0012] [3] The resin layer according to [1] or [2] above, wherein the displacement amounts d1 to d3 are each 200 nm or more and 1000 nm or less.
[0013] [4] The resin layer according to any one of [1] to [3] above, having a film thickness of 20 μm or more and 150 μm or less.
[0014] [5] A foldable laminated optical film including at least the resin layer according to any one of [1] to [4] above.
[0015] [6] The optical film according to [5] above, further comprising a functional layer provided on either the first surface or the second surface of the resin layer.
[0016] [7] The optical film according to the above [5] or [6], further comprising a resin substrate provided on either the first surface or the second surface of the resin layer.
[0017] [8] A foldable, light-transmitting optical film comprising a resin substrate and a resin layer provided on a first surface side of the resin substrate, wherein the thickness of the resin substrate is 20 μm or less, the film thickness of the resin layer is 50 μm or more, the ratio of the film thickness of the resin layer to the thickness of the resin substrate is 4.0 or more and 12.0 or less, and when an indentation test is performed in which a Berkovich indenter is pressed with a maximum load of 200 μN into a cross section in the thickness direction of the resin substrate, the displacement amount of the resin substrate is 50 nm or more and 250 nm or less, and when the indentation test is performed on a cross section in the film thickness direction of the resin layer, the displacement amount of the resin layer is 200 nm or more and 1500 nm or less.
[0018] [9] The optical film according to the above [8], wherein the resin substrate contains at least one of a polyimide-based resin, a polyamide-based resin, and a polyamideimide-based resin.
[0019]
[10] The optical film according to the above [8] or [9], further comprising a hard coat layer provided on a second surface side opposite to the first surface side of the resin substrate.
[0020]
[11] A foldable optical film for use in an image display device, comprising: a resin substrate; and a resin layer containing organic particles provided on one side of the resin substrate, wherein the surface of the resin layer is an uneven surface, and the organic particles are unevenly distributed on the resin substrate side relative to a center line that bisects the resin layer in a thickness direction of the resin layer.
[0021]
[12] The optical film according to
[11] above, wherein the resin substrate contains one or more resins selected from the group consisting of polyimide-based resins, polyamideimide-based resins, polyamide-based resins, and polyester-based resins.
[0022]
[13] The optical film according to the above
[11] or
[12] , wherein the resin layer has a thickness of 2 μm or more and 15 μm or less.
[0023]
[14] The optical film according to any one of
[11] to
[13] above, wherein the indentation hardness of a lower portion of the resin layer is smaller than the indentation hardness of an upper portion of the resin layer.
[0024]
[15] The optical film described in any one of
[11] to
[14] above, wherein the resin layer comprises a first resin layer and a second resin layer provided on the surface side of the first resin layer, and the first resin layer contains the organic particles.
[0025]
[16] The optical film according to any one of [5] to
[15] above, wherein the optical film does not crack or break when a test of folding the optical film 180° so that the distance between opposing sides of the optical film is 10 mm is repeated 100,000 times.
[0026]
[17] An image display device comprising: a display element; and the resin layer according to any one of [1] to [4] above or the optical film according to any one of [5] to
[16] above, which is disposed on the viewer side of the display element.
[0027]
[18] The image display device according to
[17] above, wherein the display element is an organic light-emitting diode element. Effect of the Invention
[0028] According to a first aspect of the present invention, it is possible to provide a resin layer having good foldability and good impact resistance, and an optical film and an image display device including the same. According to a second aspect of the present invention, it is possible to provide a foldable optical film that is less likely to develop a crease and has good impact resistance, and an image display device including the same. According to a third aspect of the present invention, it is possible to provide a foldable optical film that leaves inconspicuous pressure marks and is less likely to crack when folded, and an image display device including the same. [Brief description of the drawings]
[0029] [Figure 1] FIG. 1 is a schematic diagram of a resin layer according to the first embodiment. [Diagram 2] FIG. 2 is a partially enlarged view of the resin layer in FIG. [Diagram 3] FIG. 3 is a schematic diagram of the optical film according to the first embodiment. [Figure 4] 4(A) to 4(C) are schematic diagrams showing the state of the continuous folding test. [Diagram 5] FIG. 5 is a schematic diagram of another optical film according to the first embodiment. [Figure 6] FIG. 6 is a schematic configuration diagram of the image display device according to the first embodiment. [Figure 7] FIG. 7 is a schematic diagram of the optical film according to the second embodiment. [Figure 8] 8(A) and 8(B) are schematic diagrams showing the state of the folding static test. [Figure 9] FIG. 9 is a schematic diagram of an optical film according to the third embodiment. [Figure 10] FIG. 10 is a partially enlarged view of the optical film of FIG. [Figure 11] FIG. 11 is a schematic diagram of another optical film according to the third embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] [First embodiment] Hereinafter, the resin layer, the optical film, the optical film, and the image display device according to the first embodiment of the present invention will be described with reference to the drawings. In this specification, the terms "film" and "sheet" are not distinguished from each other based only on the difference in name. Therefore, for example, "film" is used to mean a member also called a sheet. FIG. 1 is a schematic diagram of the resin layer according to this embodiment, FIG. 2 is a partially enlarged view of the resin layer in FIG. 1, and FIG. 3 is a schematic diagram of the optical film according to this embodiment. FIG. 4 is a schematic diagram showing the state of a continuous folding test, and FIG. 5 is a schematic diagram of another optical film according to the embodiment.
[0031] <<<Resin layer>>> The resin layer 10 shown in FIG. 1 is used in an image display device and has light transmittance. In this embodiment, the "resin layer" is a layer having a single layer structure containing a resin. The resin layer 10 is made of a resin having light transmittance and has impact absorption properties. The resin layer 10 may be used alone, or may be incorporated into the optical films 30 and 50 having a laminated structure. A release film may be attached to the resin layer 10. In this specification, "light transmittance" means a property of transmitting light, and includes, for example, a total light transmittance of 50% or more, preferably 70% or more, more preferably 80% or more, and particularly preferably 90% or more. The light transmittance does not necessarily have to be transparent, and may be semi-transparent.
[0032] As shown in FIG. 2, the resin layer 10 is divided into three equal parts in the thickness direction D1 of the resin layer 10, and the first region 10C, the second region 10D, and the third region 10E are arranged in order from the first surface 10A of the resin layer 10 to the second surface 10B opposite to the first surface 10A. When a Berkovich indenter is pressed into the first region 10C, the second region 10D, and the third region 10E at a constant load in a cross section of the resin layer 10 in the thickness direction D1, the displacement amount in the first region 10C is d1, the displacement amount in the second region 10D is d2, and the displacement amount in the third region 10E is d3, the following relational formula (1) is satisfied. The resin layer of this embodiment is softer than the functional layer (hard coat layer) and the resin substrate described later and is greatly affected by viscosity, so the method of measuring the indentation hardness, Martens hardness, etc. by the nanoindentation method was not suitable. Therefore, the displacement amount is used as an index of hardness. d1 <d2<d3 …(1)
[0033] The displacements d1 to d3 can be obtained using a nanoindenter (for example, TI950 TriboIndenter manufactured by Bruker) as follows. Specifically, first, a block is prepared by embedding a resin layer cut into 1 mm×10 mm, and a uniform slice having a thickness of 70 nm to 100 nm without holes is cut out from this block by a general slice preparation method. Here, the slice having a thickness of 70 nm to 100 nm is cut out because the remaining block from which the slice is cut out is used for measurement, and by cutting out a slice of this thickness, the flatness of the cross section of the remaining block is improved. Note that if the flatness of the remaining block is poor, the measurement accuracy may be deteriorated. For example, an ultramicrotome EM UC7 manufactured by Leica Microsystems Inc. can be used to prepare the slice. Then, the remaining block from which the uniform slice without holes is cut out is used as the measurement sample. Next, in the cross section obtained by cutting out the above-mentioned slice from such a measurement sample, a Berkovich indenter (triangular pyramid, for example, TI-0039 manufactured by Bruker) is pressed vertically into the center of the thickness direction of the cross section of the first region of the resin layer with a maximum load of 200 μN for 40 seconds under the following measurement conditions, and the displacement (indentation depth) d1 at that time is measured. Here, the Berkovich indenter is pressed into a portion of the first region that is 500 nm or more away from each of the two ends of the resin layer toward the center of the resin layer in order to avoid the influence of the side edges of the resin layer. The displacement is the arithmetic average value of the values obtained by measuring at 10 points. Note that if any of the measured values deviates from the arithmetic average value by ±20% or more, that measured value is excluded and remeasured. Whether or not any of the measured values deviates from the arithmetic average value by ±20% or more is determined by whether the value (%) calculated by (AB) / B×100, where A is the measured value and B is the arithmetic average value, is ±20% or more. The displacement amounts of the second and third regions of the resin layer are measured in the same manner as the displacement amount of the first region. (Measurement conditions) Control method: Load control (maximum load 200μN) Lift amount: 0nm Preload: 0.5μN ·Loading speed: 5μN / sec Maximum load hold time: 5 seconds ·Unloading speed: 5μN / sec ·Temperature: 23±5℃ Relative humidity: 30%~70%
[0034] The ratio (d1 / d3) of the displacement amount d1 to the displacement amount d3 is preferably 0.85 or less. If d1 / d3 is 0.85 or less, it is possible to achieve both excellent foldability and impact resistance. The upper limit of d1 / d3 is more preferably 0.82 or less, or 0.80 or less, and the lower limit is preferably 0.40 or more, 0.50 or more, or 0.60 or more, in order to easily suppress the occurrence of wrinkles when bent.
[0035] The ratio of the displacement amount d1 to the displacement amount d2 (d1 / d2) is preferably 0.70 or more and 0.99 or less. If d1 / d2 is 0.70 or more, the occurrence of wrinkles during bending can be suppressed, and if d1 / d2 is 0.99 or less, both excellent foldability and impact resistance can be achieved. The lower limit of d1 / d2 is more preferably 0.75 or more, 0.80 or more, or 0.85 or more, and the upper limit is more preferably 0.95 or less, 0.92 or less, or 0.90 or less.
[0036] The ratio of the displacement amount d2 to the displacement amount d3 (d2 / d3) is preferably 0.70 or more and 0.99 or less. If d2 / d3 is 0.70 or more, the occurrence of wrinkles during bending can be suppressed, and if d2 / d3 is 0.99 or less, both excellent foldability and impact resistance can be achieved. The lower limit of d2 / d3 is more preferably 0.75 or more, 0.80 or more, or 0.85 or more, and the upper limit is more preferably 0.95 or less, 0.92 or less, or 0.90 or less.
[0037] It is preferable that the displacements d1 to d3 are each 1000 nm or less. If the displacements d1 to d3 are each 1000 nm or less, the resin layer 10 has sufficient hardness and can obtain excellent impact resistance. It is more preferable that the upper limits of the displacements d1 to d3 are each 900 nm or less, 800 nm or less, or 700 nm or less, and it is more preferable that the lower limits are each 200 nm or more, 300 nm or more, or 350 nm or more, from the viewpoint of ensuring the foldability of the resin layer 10.
[0038] The total light transmittance of the resin layer 10 is preferably 85% or more. If the total light transmittance of the resin layer 10 is 85% or more, sufficient image visibility can be obtained when the resin layer 10 is used in a mobile terminal. The total light transmittance of the resin layer 10 is more preferably 87% or more, or 90% or more.
[0039] The total light transmittance can be measured by a method conforming to JIS K7361-1:1997 using a haze meter (for example, product name "HM-150" manufactured by Murakami Color Research Laboratory Co., Ltd.) in an environment with a temperature of 23±5°C and a relative humidity of 30% to 70%. The total light transmittance is measured three times for each resin layer after cutting out the resin layer to a size of 50 mm×100 mm, placing the resin layer in a state without curls or wrinkles and without fingerprints or dust, and the arithmetic average value of the values obtained by the three measurements is used. In this specification, "measured three times" does not mean measuring the same place three times, but measuring three different places. In the resin layer 10, the first surface 10A and the second surface 10B are flat when visually observed, and the variation in film thickness is within a range of ±10%. Therefore, it is considered that the average value of the total light transmittance of the entire in-plane of the resin layer can be obtained by measuring the total light transmittance at three different places of the cut-out resin layer. The variation in total light transmittance is within ±10%, even if the measurement target is as long as 1m x 3000m, or the size of a 5-inch smartphone. If the resin layer cannot be cut out to the above size, for example, the entrance opening for measurement of the HM-150 is 20mmφ, so a sample size with a diameter of 21mm or more is required. For this reason, the resin layer may be appropriately cut out to a size of 22mm x 22mm or more. If the size of the resin layer is small, the measurement points are set to three by shifting the light source spot little by little or changing the angle within the range where it does not move.
[0040] The haze value (total haze value) of the resin layer 10 is preferably 3.0% or less. If the haze value of the resin layer is 3.0% or less, when the resin layer is used in a mobile terminal, whitening of the image display surface can be suppressed. More preferably, the haze value is 2.0% or less, 1.5% or less, 1.0% or less, or 0.5% or less.
[0041] The haze value can be measured in an environment with a temperature of 23±5° C. and a relative humidity of 30% to 70% by a method conforming to JIS K7136:2000 using a haze meter (for example, product name "HM-150" manufactured by Murakami Color Research Laboratory Co., Ltd.) Specifically, the haze value is measured by the same method as the method for measuring the total light transmittance.
[0042] The thickness of the resin layer 10 is preferably 20 μm or more and 150 μm or less. If the thickness of the resin layer 10 is 20 μm or more, it can have excellent impact resistance, and if the thickness of the resin layer 10 is 150 μm or less, the resin layer 10 is less likely to break and exhibits excellent performance in a 100,000-fold continuous folding test. The lower limit of the thickness of the resin layer 10 is more preferably 40 μm or more or 50 μm or more, and the upper limit of the resin layer 10 is more preferably 120 μm or less, 100 μm or less, 80 μm or less, or 60 μm or less, from the viewpoint of being suitable for thinning and having good processability.
[0043] The thickness of the resin layer 10 is determined by photographing a cross section of the resin layer 10 with a scanning electron microscope (SEM), measuring the thickness of the resin layer 10 at 10 points on the image of the cross section, and arithmetic mean value of the thicknesses at the 10 points.
[0044] A specific method for taking a cross-sectional photograph is described below. First, a resin layer cut into a size of 1 mm x 10 mm is embedded in an embedding resin to prepare a block, and a uniform slice having a thickness of 70 nm to 100 nm without holes is cut out from this block by a general slice preparation method. For example, an ultramicrotome EM UC7 manufactured by Leica Microsystems can be used to prepare the slice. Then, this uniform slice without holes is used as a measurement sample. Then, a cross-sectional photograph of the measurement sample is taken using a scanning transmission electron microscope (STEM). An example of a scanning transmission electron microscope (STEM) is the S-4800 manufactured by Hitachi High-Technologies Corporation. When taking a cross-sectional photograph using the S-4800, the detector is set to "SE", the acceleration voltage is set to "5 kV", and the emission current is set to "10 μA" to perform cross-sectional observation. The magnification is adjusted appropriately between 100x and 100,000x, preferably 500x and 50,000x, and more preferably 1,000x and 10,000x while observing whether the layers can be distinguished by adjusting the focus and observing the contrast and brightness. When taking a cross-sectional photograph using the S-4800, the beam monitor aperture may be set to "3", the objective lens aperture may be set to "3", and the WD may be set to "8 mm". When measuring the film thickness of the resin layer, it is important that the interface contrast between the resin layer and other layers (e.g., embedding resin) can be observed as clearly as possible when observing the cross-section. If the interface is difficult to see due to insufficient contrast, a staining process using osmium tetroxide, ruthenium tetroxide, phosphotungstic acid, etc. may be performed to make the interface between the organic layers easier to see. In addition, the contrast of the interface may be difficult to see at high magnification. In that case, observation is also performed at low magnification at the same time. For example, the film is observed at two magnifications, high and low, such as 500x and 10,000x, or 1,000x and 20,000x, and the arithmetic average value is calculated at both magnifications. The average value is then used as the film thickness of the resin layer.
[0045] The resin constituting the resin layer 10 is not particularly limited as long as it is a resin that satisfies the above-mentioned relational formula (1). Examples of such resins include cured products (polymerized products) of ionizing radiation curable compounds (ionizing radiation polymerizable compounds). Examples of ionizing radiation in this specification include visible light, ultraviolet light, X-rays, electron beams, α rays, β rays, and γ rays. Examples of cured products of ionizing radiation curable compounds include urethane-based resins and silicone-based resins.
[0046] (Urethane resin) The urethane resin is a resin having a urethane bond. Examples of the urethane resin include a cured product of an ionizing radiation curable urethane resin composition and a cured product of a thermosetting urethane resin composition. Among these, a cured product of an ionizing radiation curable urethane resin composition is preferred from the viewpoints of obtaining high hardness, a fast curing speed, and excellent mass productivity.
[0047] The ionizing radiation curable urethane resin composition contains a urethane (meth)acrylate, and the thermosetting urethane resin composition contains a polyol compound and an isocyanate compound. The urethane (meth)acrylate, the polyol compound, and the isocyanate compound may be any one of a monomer, an oligomer, and a prepolymer.
[0048] The number of (meth)acryloyl groups (functional groups) in the urethane (meth)acrylate is preferably 2 or more and 4 or less. If the number of (meth)acryloyl groups in the urethane (meth)acrylate is less than 2, the pencil hardness may be low, and if it exceeds 4, the curing shrinkage may be large, the optical film may curl, and the resin layer may crack when folded. It is more preferable that the upper limit of the number of (meth)acryloyl groups in the urethane (meth)acrylate is 3 or less. The term "(meth)acryloyl group" includes both "acryloyl group" and "methacryloyl group".
[0049] The weight average molecular weight of the urethane (meth)acrylate is preferably 1500 or more and 20000 or less. If the weight average molecular weight of the urethane (meth)acrylate is less than 1500, the impact resistance may decrease, and if it exceeds 20000, the viscosity of the ionizing radiation curable urethane resin composition may increase, resulting in poor coatability. The lower limit of the weight average molecular weight of the urethane (meth)acrylate is more preferably 2000 or more, and the upper limit is more preferably 15000 or less.
[0050] Examples of the repeating unit having a structure derived from a urethane (meth)acrylate include structures represented by the following general formula (1), (2), (3) or (4). [ka] In the above general formula (1), R 1 represents a branched alkyl group, and R 2 represents a branched alkyl group or a saturated cyclic aliphatic group, R 3 represents a hydrogen atom or a methyl group, R 4 represents a hydrogen atom, a methyl group or an ethyl group, m represents an integer of 0 or more, and x represents an integer of 0 to 3.
[0051] [ka] In the above general formula (2), R 1 represents a branched alkyl group, and R 2 represents a branched alkyl group or a saturated cyclic aliphatic group, R 3 represents a hydrogen atom or a methyl group, R 4 represents a hydrogen atom, a methyl group or an ethyl group, n represents an integer of 1 or more, and x represents an integer of 0 to 3.
[0052] [ka] In the above general formula (3), R 1 represents a branched alkyl group, and R 2 represents a branched alkyl group or a saturated cyclic aliphatic group, R3 represents a hydrogen atom or a methyl group, R 4 represents a hydrogen atom, a methyl group or an ethyl group, m represents an integer of 0 or more, and x represents an integer of 0 to 3.
[0053] [ka] In the above general formula (4), R 1 represents a branched alkyl group, and R 2 represents a branched alkyl group or a saturated cyclic aliphatic group, R 3 represents a hydrogen atom or a methyl group, R 4 represents a hydrogen atom, a methyl group or an ethyl group, n represents an integer of 1 or more, and x represents an integer of 0 to 3.
[0054] The structure of the polymer chain (repeating unit) of the resin constituting the resin layer 10 can be determined by analyzing the resin layer 10 by, for example, pyrolysis gas chromatography mass spectrometry (GC-MS) and Fourier transform infrared spectroscopy (FT-IR). In particular, pyrolysis GC-MS is useful because it can detect the monomer units contained in the resin layer 10 as monomer components.
[0055] The resin layer 10 may contain, in addition to the resin, an ultraviolet absorbing agent, a spectral transmittance adjusting agent, an antifouling agent, inorganic particles and / or organic particles, and the like.
[0056] <<<Optical films>>> The optical film 30 shown in FIG. 3 is a film with a laminated structure, and includes at least a resin layer 10. In addition to the resin layer 10, the optical film 30 further includes a functional layer 31 provided on either the first surface 10A or the second surface 10B of the resin layer 10. In this specification, the term "functional layer" refers to a layer that exhibits some function. The functional layer 31 has a single-layer structure, but may also have a multi-layer structure of two or more layers. In addition, the optical film 30 does not have a substrate.
[0057] The optical film 30 is foldable. Specifically, even if the optical film 30 is repeatedly subjected to a folding test (continuous folding test) described below 100,000 times, 200,000 times, 500,000 times, or 1 million times in an environment with a temperature of 23±5° C. and a relative humidity of 30% or more and 70% or less, it is preferable that the optical film 30 does not crack or break. If the optical film 30 is repeatedly subjected to the continuous folding test 100,000 times and cracks, breaks, or the like occur in the optical film 30, the foldability of the optical film 30 becomes insufficient. The reason why the number of folding times in the continuous folding test is evaluated at least 100,000 times is as follows. For example, assuming that the optical film is incorporated into a foldable smartphone, the frequency of folding (frequency of opening and closing) becomes very high. For this reason, if the number of folding times in the continuous folding test is, for example, 10,000 times or 50,000 times, evaluation at a practical level may not be possible. Specifically, for example, assuming that a person who always uses a smartphone opens and closes the smartphone 5 to 10 times just during the morning commute on a train or bus, it is assumed that the smartphone is opened and closed at least 30 times in a single day. Therefore, assuming that the smartphone is opened and closed 30 times a day, a continuous folding test with 10,000 folding times is 30 times x 365 days = 10950 times, which is a test assuming one year of use. That is, even if the result of the continuous folding test with 10,000 folding times is good, after one year has passed, there is a risk that the optical film will develop creases or cracks. Therefore, the evaluation of the continuous folding test with 10,000 folding times is only a level that cannot be used as a product, and even products that are usable but insufficient will be good and cannot be evaluated. Therefore, in order to evaluate whether or not it is at a practical level, the number of folding times in the continuous folding test needs to be at least 100,000 times. It is more preferable that the bent part does not deform when the continuous folding test is performed on the optical film 30.The continuous folding test may be performed by folding the optical film 30 so that surface 30A is on the outside, or may be performed by folding the optical film 30 so that surface 30A is on the inside, but in either case, it is preferable that the optical film 30 does not crack or break.
[0058] The continuous folding test is carried out as follows. As shown in FIG. 4(A), in the continuous folding test, first, a sample S having a size of 30 mm×100 mm is cut out from the optical film 30. If a sample S having a size of 30 mm×100 mm cannot be cut out from the optical film 30, the sample S may be cut out to a size of, for example, 10 mm×100 mm. Then, a side portion S1 of the cut-out sample S and a side portion S2 opposite to the side portion S1 are fixed by fixing parts 40 and 45 of a folding durability tester (for example, product name "U-shaped stretch tester DLDMLH-FS", manufactured by Yuasa System Devices Co., Ltd., compliant with IEC62715-6-1) arranged in parallel. Fixing by the fixing parts 40 and 45 is carried out by holding a portion of the sample S of about 10 mm on one side in the longitudinal direction of the sample S. However, if the sample S is smaller than the above size, and the portion of the sample S required for fixing is up to about 20 mm, it can be measured by attaching it to the fixing parts 40, 45 with tape. As shown in Fig. 4(A), the fixing part 40 is slidable in the horizontal direction. The above device is preferable because it makes it possible to evaluate the durability against bending load without generating tension or friction in the sample, unlike the conventional method of wrapping the sample around a rod.
[0059] Next, as shown in FIG. 4(B), the fixing portion 40 is moved closer to the fixing portion 45, thereby deforming the central portion of the sample S by folding it, and further, as shown in FIG. 4(C), the fixing portion 40 is moved to a position where the distance φ between the two opposing sides S1, S2 of the sample S fixed by the fixing portions 40, 45 is 10 mm, and then the fixing portion 40 is moved in the opposite direction to eliminate the deformation of the optical film 30.
[0060] As shown in Figs. 4(A) to (C), the center of the sample S can be folded 180° by moving the fixing part 40. The interval φ between the two opposing sides S1 and S2 of the sample S can be set to 10 mm by performing a continuous folding test under the following conditions so that the bent part S3 of the sample S does not protrude from the lower ends of the fixing parts 40 and 45, and controlling the interval φ when the fixing parts 40 and 45 are closest to each other. In this case, the outer diameter of the bent part S3 is considered to be 10 mm. It is preferable that the sample S does not crack or break when a continuous folding test in which the sample S is folded 180° so that the interval φ between the opposing sides S1 and S2 of the sample S is 10 mm is repeatedly performed 100,000 times, but it is more preferable that the sample S does not crack or break when a continuous folding test in which the sample S is folded 180° so that the interval φ between the opposing sides S1 and S2 of the sample S is 8 mm or 6 mm is repeatedly performed 100,000 times. (Folding conditions) Reciprocating speed: 40 rpm (revolutions per minute) Test stroke: 60mm Bending angle: 180°
[0061] The surface 30A of the optical film 30 (surface 31A of the functional layer 31) preferably has a hardness (pencil hardness) of 3H or more, more preferably 4H or more, when measured by a pencil hardness test specified in JIS K5600-5-4:1999. The pencil hardness test is performed by fixing the optical film 30 cut into a size of 30 mm x 100 mm on a glass plate with Cellotape (registered trademark) manufactured by Nichiban Co., Ltd. so as not to fold or wrinkle, and using a pencil hardness tester (for example, product name "Pencil Scratch Coating Hardness Tester (Electric)" manufactured by Toyo Seiki Seisakusho Co., Ltd.) to the surface 30A of the optical film 30 in an environment of a temperature of 23 ± 5 ° C. and a relative humidity of 30% to 70% by applying a load of 750 g to a pencil (for example, product name "Uni" manufactured by Mitsubishi Pencil Co., Ltd.) and moving the pencil at a moving speed of 1 mm / sec. The pencil hardness is defined as the highest hardness that does not scratch the surface of the optical film in the pencil hardness test. When measuring the pencil hardness, multiple pencils with different hardnesses are used, and the pencil hardness test is performed five times for each pencil. If the surface of the optical film is not scratched four or more times out of the five, it is determined that the pencil of this hardness did not scratch the surface of the optical film. The above scratches refer to those that are visually observed when the surface of the optical film that has been subjected to the pencil hardness test is observed through a fluorescent lamp.
[0062] The total light transmittance of the optical film 30 is preferably 85% or more, and more preferably 87% or more, 88% or more, or 90% or more, for the same reasons as those explained in the section of the resin layer 10. The total light transmittance of the optical film 30 is measured by the same method as that for measuring the total light transmittance of the resin layer 10.
[0063] The haze value (total haze value) of the optical film 30 is preferably 3.0% or less, and more preferably 2.0% or less, 1.5% or less, 1.0% or less, or 0.5% or less, for the same reasons as those explained in the section of the resin layer 10. The haze value of the optical film 30 is measured by the same method as that for the resin layer 10.
[0064] In the case where another film such as a polarizing plate is provided on the front surface 30A side or the back surface 30B side of the optical film 30 via an adhesive layer or a bonding layer, the other film is peeled off together with the adhesive layer or the bonding layer before carrying out the folding test, the total light transmittance measurement, the haze value measurement, etc. Even if such a peeling step is performed, it does not have a significant effect on these tests and measurements. The haze value is measured after the adhesive layer or the bonding layer is peeled off and any dirt on the adhesive layer or the bonding layer is thoroughly wiped off with alcohol.
[0065] The use of the optical film 30 is not particularly limited, but examples of the use of the optical film 30 include image display devices such as smartphones, tablet terminals, personal computers (PCs), wearable terminals, digital signage, televisions, and car navigation systems. The optical film 30 is also suitable for in-vehicle use. The form of each of the above image display devices is also preferable for use in applications that require flexibility, such as foldable and rollable.
[0066] The optical film 30 may be cut to a desired size, or may be in a roll shape. When the optical film 30 is cut to a desired size, the size of the optical film is not particularly limited and is appropriately determined according to the size of the display surface of the image display device. Specifically, the size of the optical film 30 may be, for example, 2.8 inches or more and 500 inches or less. In this specification, "inch" means the length of the diagonal line when the optical film is rectangular, the diameter when the optical film is circular, and the average value of the sum of the short diameter and the long diameter when the optical film is elliptical. Here, when the optical film is rectangular, the aspect ratio of the optical film when calculating the above inch is not particularly limited as long as it does not cause any problem as a display screen of the image display device. For example, length:width = 1:1, 4:3, 16:10, 16:9, 2:1, etc. can be mentioned. However, in particular, in-vehicle applications and digital signage that are rich in design, such aspect ratios are not limited. Furthermore, when the size of the optical film 30 is large, it is cut into A5 size (148 mm x 210 mm) from an arbitrary position, and then cut into the size of each measurement item. For example, when the optical film 30 is in a roll, a predetermined length is unwound from the roll of the optical film 30, and the desired size is cut from the effective area near the center where the quality is stable, not from the non-effective area including both ends extending along the longitudinal direction of the roll.
[0067] The optical film 30 may be disposed inside the image display device, but is preferably disposed near the surface of the image display device. When used near the surface of the image display device, the optical film 30 functions as a cover film (window film) used in place of a cover glass.
[0068] <<Functional Layer>> The functional layer 31 is preferably provided on the first surface 10A side, i.e., the first region 10C side, of the resin layer 10. By providing the functional layer 31 on the first region 10C side in this manner, excellent scratch resistance is achieved without impairing excellent foldability.
[0069] The functional layer 31 shown in FIG. 3 is a layer for imparting hardness to the optical film 30, and specifically, functions as a hard coat layer. However, the functional layer 31 may be a layer having other functions. In this embodiment, the "hard coat layer" refers to a layer having a Martens hardness (HM) of 375 MPa or more at the center of the cross section of the functional layer. In this specification, the "Martens hardness" refers to the hardness when an indenter is pressed 500 nm by hardness measurement using a nanoindentation method. The measurement of the Martens hardness using the nanoindentation method is performed using a "TI950 TriboIndenter" manufactured by Bruker on an optical film cut into a size of 30 mm x 30 mm. That is, under the following measurement conditions, a Berkovich indenter (triangular pyramid, for example, TI-0039 manufactured by Bruker) is pressed 500 nm perpendicularly into the cross section of the functional layer. Here, in order to avoid the influence of the side edges of the resin layer and the functional layer, the Berkovich indenter is pressed into a portion of the functional layer that is 500 nm away from the interface between the resin layer and the functional layer toward the center of the functional layer and 500 nm or more away from each of the two ends of the functional layer toward the center of the functional layer. After that, the residual stress is relaxed by holding it constant, and then the load is removed and the maximum load after relaxation is measured, and the maximum load P max and the area A of the depression with a depth of 500 nm, max Martens hardness is calculated by multiplying the measured value by (AB) / B x 100 (%). Martens hardness is the arithmetic average of the values obtained by measuring at 10 locations. If any of the measured values deviate from the arithmetic average by more than ±20%, those values are to be excluded and remeasured. Whether or not any of the measured values deviate from the arithmetic average by more than ±20% is determined by whether the value (%) calculated by (AB) / B x 100, where A is the measured value and B is the arithmetic average, is more than ±20%. (Measurement conditions) Control method: Displacement control ·Loading speed: 10nm / sec ·Holding time: 5 seconds ·Loading and unloading speed: 10nm / sec ·Measurement temperature: 23±5℃ ·Measurement humidity: 30%~70%
[0070] The Martens hardness of the functional layer 31 is preferably 375 MPa or more and 1500 MPa or less. If the Martens hardness of the functional layer 31 is 375 MPa or more, good hardness can be obtained, and if it is 1500 MPa or less, good folding performance can be obtained.
[0071] The thickness of the functional layer 31 is preferably 3 μm or more and 10 μm or less. If the thickness of the functional layer 31 is 3 μm or more, good hardness can be obtained, and if it is 10 μm or less, deterioration of processability can be suppressed. In this specification, the "thickness of the functional layer" means the thickness (total thickness) of the functional layer when the functional layer has a multi-layer structure. The lower limit of the thickness of the functional layer 31 is more preferably 4 μm or more, or 5 μm or more, and the upper limit is more preferably 8 μm or less, or 7 μm or less.
[0072] The thickness of the functional layer 31 is measured by photographing a cross section of the functional layer 31 using a scanning transmission electron microscope (STEM) or a transmission electron microscope (TEM), measuring the thickness of the functional layer 31 at 10 points on the image of the cross section, and calculating the arithmetic average value of the thicknesses at the 10 points. When measuring the thickness of the functional layer 31, first, a measurement sample is prepared by the same method as that for the resin layer 10. Then, a cross-sectional photograph of the measurement sample is taken using a scanning transmission electron microscope (STEM) (for example, product name "S-4800" manufactured by Hitachi High-Technologies Corporation). When taking a cross-sectional photograph using the S-4800, the detector is set to "TE", the acceleration voltage is set to "30 kV", and the emission current is set to "10 μA" to observe the cross section. The magnification is adjusted appropriately between 5,000 times and 200,000 times while adjusting the focus and observing whether the contrast and brightness of each layer can be distinguished. The preferred magnification is 10,000 to 100,000, more preferably 10,000 to 50,000, and most preferably 25,000 to 50,000. When taking a cross-sectional photograph using the S-4800, the beam monitor aperture may be set to "3", the objective lens aperture may be set to "3", and the WD may be set to "8 mm". When measuring the film thickness of the functional layer, it is important that the interface contrast between the functional layer and other layers (e.g., resin layer) can be observed as clearly as possible when observing the cross-section. If the interface is difficult to see due to insufficient contrast, a dyeing process using osmium tetroxide, ruthenium tetroxide, tungstophosphoric acid, or the like may be performed to make the interface between the organic layers easier to see, so a dyeing process may be performed. In addition, the contrast of the interface may be difficult to see at higher magnifications. In that case, observation is also performed at lower magnifications. For example, the film is observed at two magnifications, high and low, such as 25,000x and 50,000x, or 50,000x and 100,000x, and the arithmetic average value described above is calculated at both magnifications, and this average value is used as the film thickness value of the functional layer.
[0073] The functional layer 31 preferably further contains a resin and inorganic particles dispersed in the resin.
[0074] <Resin> The resin contains a polymer (cured product) of a polymerizable compound (curable compound). The polymerizable compound has at least one polymerizable functional group in the molecule. Examples of the polymerizable functional group include ethylenically unsaturated groups such as (meth)acryloyl group, vinyl group, and allyl group.
[0075] The polymerizable compound is preferably a polyfunctional (meth)acrylate. Examples of the polyfunctional (meth)acrylate include trimethylolpropane tri(meth)acrylate, tripropylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and the like. acrylate, tripentaerythritol octa(meth)acrylate, tetrapentaerythritol deca(meth)acrylate, isocyanuric acid tri(meth)acrylate, isocyanuric acid di(meth)acrylate, polyester tri(meth)acrylate, polyester di(meth)acrylate, bisphenol di(meth)acrylate, diglycerin tetra(meth)acrylate, adamantyl di(meth)acrylate, isobornyl di(meth)acrylate, dicyclopentane di(meth)acrylate, tricyclodecane di(meth)acrylate, and those modified with PO, EO, caprolactone, etc.
[0076] Among these, those having three to six functional groups are preferred because they can suitably satisfy the above-mentioned Martens hardness, and examples thereof include pentaerythritol triacrylate (PETA), dipentaerythritol hexaacrylate (DPHA), pentaerythritol tetraacrylate (PETTA), dipentaerythritol pentaacrylate (DPPA), trimethylolpropane tri(meth)acrylate, tripentaerythritol octa(meth)acrylate, and tetrapentaerythritol deca(meth)acrylate. In this specification, (meth)acrylate means acrylate and methacrylate.
[0077] In addition, the composition may further contain a monofunctional (meth)acrylate monomer in order to adjust the hardness or viscosity of the composition, improve adhesion, etc. Examples of the monofunctional (meth)acrylate monomer include hydroxyethyl acrylate (HEA), glycidyl methacrylate, methoxypolyethylene glycol (meth)acrylate, isostearyl (meth)acrylate, 2-acryloyloxyethyl succinate, acryloylmorpholine, N-acryloyloxyethylhexahydrophthalimide, cyclohexyl acrylate, tetrahydrofuryl acrylate, isobornyl acrylate, phenoxyethyl acrylate, and adamantyl acrylate.
[0078] From the viewpoint of improving the hardness of the resin layer, the weight average molecular weight of the monomer is preferably less than 1000, and more preferably from 200 to 800. The weight average molecular weight of the polymerizable oligomer is preferably from 1000 to 20,000, more preferably from 1000 to 10,000, and even more preferably from 2000 to 7000.
[0079] <Inorganic particles> The inorganic particles are not particularly limited as long as they can improve hardness, but from the viewpoint of obtaining excellent hardness, silica particles are preferred. Among the silica particles, reactive silica particles are preferred. The reactive silica particles are silica particles that can form a crosslinked structure with the polyfunctional (meth)acrylate, and the hardness of the functional layer 31 can be sufficiently increased by including the reactive silica particles.
[0080] The reactive silica particles preferably have a reactive functional group on the surface thereof, and as the reactive functional group, for example, the above-mentioned polymerizable functional group is preferably used.
[0081] The reactive silica particles are not particularly limited, and conventionally known ones can be used, for example, the reactive silica particles described in JP-A-2008-165040, etc. In addition, commercially available reactive silica particles include, for example, MIBK-SD, MIBK-SD-MS, MIBK-SD-L, MIBK-SD-ZL (all manufactured by Nissan Chemical Industries, Ltd.), V8802, V8803 (all manufactured by JGC Catalysts and Chemicals, Ltd.), etc.
[0082] The silica particles may be spherical silica particles, but are preferably irregular silica particles. Spherical silica particles and irregular silica particles may be mixed. In this specification, "spherical silica particles" refers to silica particles such as spherical or elliptical silica particles, and "irregular silica particles" refers to silica particles having random irregularities on the surface in the shape of a potato (aspect ratio of 1.2 to 40 when observed in cross section). The irregular silica particles have a larger surface area than spherical silica particles, so that the contact area with the polyfunctional (meth)acrylate, etc. is increased by including such irregular silica particles, and the hardness of the hard coat layer can be improved. Whether the silica particles contained in the functional layer are irregular silica particles can be confirmed by observing the cross section of the functional layer with a transmission electron microscope (TEM) or a scanning transmission electron microscope (STEM).
[0083] The average particle diameter of the silica particles is preferably 5 nm or more and 200 nm or less. If the average particle diameter of the silica particles is 5 nm or more, the particles themselves are not difficult to manufacture, the aggregation of the particles can be suppressed, and it is not difficult to make them into irregular shapes. On the other hand, if the average particle diameter of the irregularly shaped silica particles is 200 nm or less, the formation of large irregularities in the functional layer can be suppressed, and the increase in haze can also be suppressed. When the silica particles are spherical silica particles, the average particle diameter of the silica particles is determined by measuring the particle diameters of 20 particles from an image of the cross section of the particles taken using a transmission electron microscope (TEM) or a scanning transmission electron microscope (STEM), and the arithmetic average value of the particle diameters of the 20 particles is used. In addition, when the silica particles are irregularly shaped silica particles, the average particle diameter of the silica particles is determined by measuring the maximum (long axis) and minimum (short axis) of the distance between two points on the outer periphery of the particles from an image of the cross section of the hard coat layer taken using a transmission electron microscope (TEM) or a scanning transmission electron microscope (STEM), averaging them, and determining the particle diameter as the arithmetic mean value of the particle diameters of 20 particles.
[0084] By controlling the size and amount of the inorganic particles, it is possible to control the hardness (Martens hardness) of the functional layer 31. For example, when forming the functional layer 31, it is preferable that the silica particles have a diameter of 5 nm or more and 200 nm or less, and are present in an amount of 25 to 60 parts by mass relative to 100 parts by mass of the polymerizable compound.
[0085] The functional layer 31 may contain materials other than the above-mentioned materials within a range that satisfies the above-mentioned Martens hardness. For example, the resin component may contain a polymerizable monomer or a polymerizable oligomer that forms a cured product by irradiation with ionizing radiation. Examples of the above-mentioned polymerizable monomer or polymerizable oligomer include a (meth)acrylate monomer having a radical polymerizable unsaturated group in the molecule, or a (meth)acrylate oligomer having a radical polymerizable unsaturated group in the molecule. Examples of the above-mentioned (meth)acrylate monomer having a radical polymerizable unsaturated group in the molecule or a (meth)acrylate oligomer having a radical polymerizable unsaturated group in the molecule include monomers or oligomers such as urethane (meth)acrylate, polyester (meth)acrylate, epoxy (meth)acrylate, melamine (meth)acrylate, polyfluoroalkyl (meth)acrylate, and silicone (meth)acrylate. These polymerizable monomers or polymerizable oligomers may be used alone or in combination of two or more. Among these, polyfunctional (six or more functional) urethane (meth)acrylates having a weight average molecular weight of 1,000 to 10,000 are preferred.
[0086] The functional layer 31 may further include an ultraviolet absorbing agent, a spectral transmittance adjusting agent, and / or an antifouling agent.
[0087] <<<Other optical films>>> The optical film 30 shown in Fig. 3 does not include a substrate, but may include a substrate like the optical film 50 shown in Fig. 5. As shown in Fig. 5, the optical film 50 includes a resin layer 10, a resin substrate 51, and a functional layer 52, in this order. The resin substrate 51 is preferably provided on the first surface 10A side of the resin layer 10. In the optical film 50, the resin layer 10 is provided directly on the resin substrate 51, but may be attached to the resin substrate via an adhesive layer.
[0088] The surface 50A of the optical film 50 is the surface 52A of the functional layer 52. In this specification, the surface of the optical film is used to mean one side of the optical film, and the surface opposite to the surface of the optical film is referred to as the back surface to distinguish it from the front surface of the optical film. The back surface 50B of the optical film 50 is the second surface 10B of the resin layer 10.
[0089] The optical film 50 is also foldable, similarly to the optical film 30. The preferred number of folding times, the preferred distance φ between opposing sides, and the conditions for the continuous folding test are similar to those of the optical film 30, and therefore will not be described here.
[0090] The surface 50A of the optical film 50 (surface 52A of the functional layer 52) preferably has a hardness (pencil hardness) of 2B or more when measured by the pencil hardness test specified in JIS K5600-5-4: 1999. The pencil hardness of the optical film 50 is measured by the same method as that of the optical film 30.
[0091] The optical film 50 preferably has a yellow index (YI) of 15 or less. If the YI of the optical film 50 is 15 or less, the yellowish tinge of the optical film can be suppressed, and the optical film can be applied to applications requiring transparency. The upper limit of the yellow index (YI) of the optical film 50 is more preferably 10 or less, 5 or less, or 1.5 or less. The yellow index (YI) is a value calculated from the chromaticity tristimulus values X, Y, and Z of the optical film cut to a size of 50 mm x 100 mm, measured in a spectrophotometer (e.g., product name "UV-2450" manufactured by Shimadzu Corporation, light source: tungsten lamp and deuterium lamp) in an environment of temperature 23 ± 5 ° C. and relative humidity 30% to 70%, with the resin layer side of the optical film being placed on the light source side, according to the calculation formula described in JIS Z8722: 2009. The tristimulus values X, Y, and Z are calculated according to the calculation formula described in ASTM D1925: 1962. The upper limit of the yellow index (YI) of the optical film 50 is more preferably 10 or less. The yellow index (YI) is the arithmetic average value of the values obtained by measuring three times for one optical film. In addition, in UV-2450, the yellow index is calculated by reading the above transmittance measurement data on the monitor connected to the UV-2450 and checking the "YI" item in the calculation items. The transmittance at wavelengths of 300nm to 780nm is measured under the following conditions by measuring the transmittance at at least 5 points within 1nm before and after each wavelength of 300nm to 780nm and calculating the average value. If the spectrum of the spectral transmittance appears to be wavy, smoothing processing may be performed with a delta of 5.0nm. (Measurement conditions) ·Wavelength range: 300nm~780nm Scan speed: Fast Slit width: 2.0 Sampling interval: Auto (0.5 nm interval) ·Lighting:C Light source: D2 and WI ·Field of view: 2° Light source switching wavelength: 360nm S / R Switching: Standard Detector: PM Autozero: Performed at 550 nm after baseline scan
[0092] The total light transmittance of the optical film 50 is preferably 85% or more, more preferably 87% or more, or even 90% or more, for the same reasons as those explained in the section of the resin layer 10. The total light transmittance of the optical film 50 is measured by the same method as that for measuring the total light transmittance of the resin layer 10.
[0093] The haze value (total haze value) of the optical film 50 is preferably 3.0% or less, and more preferably 2.0% or less, 1.5% or less, 1.0% or less, or 0.5% or less, for the same reasons as those explained in the section of the resin layer 10. The haze value of the optical film 50 is measured by the same method as that for the resin layer 10.
[0094] <<Resin substrate>> Resin base material 51 has optical transparency. Resin base material 51 preferably contains one or more resins selected from the group consisting of polyimide resins, polyamideimide resins, polyamide resins, and polyester resins (e.g., polyethylene terephthalate resins and polyethylene naphthalate resins).
[0095] Among these resins, polyimide-based resins, polyamide-based resins, or mixtures thereof are preferred, since they are not only less likely to crack or break in a continuous folding test, but also have excellent hardness and transparency, and are also excellent in heat resistance, and can be imparted with even better hardness and transparency by baking.
[0096] The polyimide resin is obtained by reacting a tetracarboxylic acid component with a diamine component. The polyimide resin is not particularly limited, but it is preferable that the polyimide resin has at least one structure selected from the group consisting of structures represented by the following general formula (5) and the following general formula (7) in terms of excellent light transmittance and excellent rigidity.
[0097] [ka] In the above general formula (5), R 5 is a tetravalent group which is a tetracarboxylic acid residue, R 6 represents at least one divalent group selected from the group consisting of trans-cyclohexanediamine residue, trans-1,4-bismethylenecyclohexanediamine residue, 4,4'-diaminodiphenylsulfone residue, 3,4'-diaminodiphenylsulfone residue, and divalent groups represented by the following general formula (6). n represents the number of repeating units and is 1 or more. In this specification, the term "tetracarboxylic acid residue" refers to a residue obtained by removing four carboxyl groups from a tetracarboxylic acid, and represents the same structure as the residue obtained by removing an acid dianhydride structure from a tetracarboxylic dianhydride. In addition, the term "diamine residue" refers to a residue obtained by removing two amino groups from a diamine.
[0098] [ka] In the above general formula (6), R 7 and R 8 each independently represents a hydrogen atom, an alkyl group, or a perfluoroalkyl group.
[0099] [ka] In the above general formula (7), R 9R represents at least one tetravalent group selected from the group consisting of a cyclohexanetetracarboxylic acid residue, a cyclopentanetetracarboxylic acid residue, a dicyclohexane-3,4,3',4'-tetracarboxylic acid residue, and a 4,4'-(hexafluoroisopropylidene)diphthalic acid residue; 10 represents a divalent group which is a diamine residue, and n' represents the number of repeating units and is 1 or more.
[0100] In the above general formula (5), R 5 R in the above general formula (5) is a tetracarboxylic acid residue, and can be a residue obtained by removing the acid dianhydride structure from the tetracarboxylic acid dianhydride as exemplified above. 5 Among them, from the viewpoint of improving light transmittance and improving rigidity, it is preferable to include at least one selected from the group consisting of 4,4'-(hexafluoroisopropylidene)diphthalic acid residue, 3,3',4,4'-biphenyltetracarboxylic acid residue, pyromellitic acid residue, 2,3',3,4'-biphenyltetracarboxylic acid residue, 3,3',4,4'-benzophenonetetracarboxylic acid residue, 3,3',4,4'-diphenylsulfonetetracarboxylic acid residue, 4,4'-oxydiphthalic acid residue, cyclohexanetetracarboxylic acid residue, and cyclopentanetetracarboxylic acid residue, and it is further preferable to include at least one selected from the group consisting of 4,4'-(hexafluoroisopropylidene)diphthalic acid residue, 4,4'-oxydiphthalic acid residue, and 3,3',4,4'-diphenylsulfonetetracarboxylic acid residue.
[0101] R 5 In the present invention, the total amount of these suitable residues is preferably 50 mol % or more, more preferably 70 mol % or more, and even more preferably 90 mol % or more.
[0102] Also, R 5It is also preferable to use a mixture of a tetracarboxylic acid residue group (Group A) suitable for improving rigidity, such as at least one selected from the group consisting of 3,3',4,4'-biphenyltetracarboxylic acid residues, 3,3',4,4'-benzophenonetetracarboxylic acid residues, and pyromellitic acid residues, and a tetracarboxylic acid residue group (Group B) suitable for improving transparency, such as at least one selected from the group consisting of 4,4'-(hexafluoroisopropylidene)diphthalic acid residues, 2,3',3,4'-biphenyltetracarboxylic acid residues, 3,3',4,4'-diphenylsulfonetetracarboxylic acid residues, 4,4'-oxydiphthalic acid residues, cyclohexanetetracarboxylic acid residues, and cyclopentanetetracarboxylic acid residues.
[0103] In this case, the content ratio of the tetracarboxylic acid residue group suitable for improving the rigidity (Group A) to the tetracarboxylic acid residue group suitable for improving the transparency (Group B) is preferably 0.05 mol or more and 9 mol or less, more preferably 0.1 mol or more and 5 mol or less, and even more preferably 0.3 mol or more and 4 mol or less, of the tetracarboxylic acid residue group suitable for improving the rigidity (Group A) per 1 mol of the tetracarboxylic acid residue group suitable for improving the transparency (Group B).
[0104] R in the above general formula (5) 6 Among them, from the viewpoint of improving light transmittance and improving rigidity, it is preferable that R is at least one divalent group selected from the group consisting of 4,4'-diaminodiphenyl sulfone residue, 3,4'-diaminodiphenyl sulfone residue, and divalent groups represented by the above general formula (6), and further, 4,4'-diaminodiphenyl sulfone residue, 3,4'-diaminodiphenyl sulfone residue, and R 7 and R 8 is preferably at least one divalent group selected from the group consisting of divalent groups represented by the above general formula (6), which is a perfluoroalkyl group.
[0105] R in the above general formula (7)9 Among these, from the viewpoints of improving light transmittance and improving rigidity, it is preferable that the diphthalic acid residue contains 4,4'-(hexafluoroisopropylidene)diphthalic acid residue, 3,3',4,4'-diphenylsulfonetetracarboxylic acid residue, and oxydiphthalic acid residue.
[0106] R 9 In the above, these suitable residues are preferably contained in an amount of 50 mol % or more, more preferably 70 mol % or more, and even more preferably 90 mol % or more.
[0107] R in the above general formula (7) 10 R in the above general formula (7) is a diamine residue, and can be a residue obtained by removing two amino groups from the diamines listed above. 10 Among them, from the viewpoints of improving light transmittance and improving rigidity, 2,2'-bis(trifluoromethyl)benzidine residue, bis[4-(4-aminophenoxy)phenyl]sulfone residue, 4,4'-diaminodiphenyl sulfone residue, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane residue, bis[4-(3-aminophenoxy)phenyl]sulfone residue, 4,4'-diamino-2,2'-bis(trifluoromethyl)diphenyl ether residue, 1,4-bis[4-amino-2-(trifluoromethyl)phenoxy]benzene residue, 2,2-bis[4-(4-amino-2-trifluoromethyl) It is preferable that the aryl group contains at least one divalent group selected from the group consisting of a 2,2'-bis(trifluoromethyl)benzidine residue, a bis[4-(4-aminophenoxy)phenyl]hexafluoropropane residue, a 4,4'-diamino-2-(trifluoromethyl)diphenyl ether residue, a 4,4'-diaminobenzanilide residue, an N,N'-bis(4-aminophenyl)terephthalamide residue, and a 9,9-bis(4-aminophenyl)fluorene residue, and it is further preferable that the aryl group contains at least one divalent group selected from the group consisting of a 2,2'-bis(trifluoromethyl)benzidine residue, a bis[4-(4-aminophenoxy)phenyl]sulfone residue, and a 4,4'-diaminodiphenyl sulfone residue.
[0108] R10 In the present invention, the total amount of these suitable residues is preferably 50 mol % or more, more preferably 70 mol % or more, and even more preferably 90 mol % or more.
[0109] Also, R 10 and a diamine residue group (Group C) suitable for improving rigidity, such as at least one selected from the group consisting of bis[4-(4-aminophenoxy)phenyl]sulfone residue, 4,4'-diaminobenzanilide residue, N,N'-bis(4-aminophenyl)terephthalamide residue, paraphenylenediamine residue, metaphenylenediamine residue, and 4,4'-diaminodiphenylmethane residue; and a diamine residue group (Group C) suitable for improving rigidity, such as at least one selected from the group consisting of 2,2'-bis(trifluoromethyl)benzidine residue, 4,4'-diaminodiphenylsulfone residue, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane residue, bis[4-(3-aminophenoxy)phenyl]hexafluoropropane residue, It is also preferred to use a mixture of diamine residues suitable for improving transparency (Group D), such as at least one selected from the group consisting of 4,4'-diamino-2,2'-bis(trifluoromethyl)diphenyl ether residue, 1,4-bis[4-amino-2-(trifluoromethyl)phenoxy]benzene residue, 2,2-bis[4-(4-amino-2-trifluoromethylphenoxy)phenyl]hexafluoropropane residue, 4,4'-diamino-2-(trifluoromethyl)diphenyl ether residue, and 9,9-bis(4-aminophenyl)fluorene residue.
[0110] In this case, the content ratio of the diamine residue group suitable for improving rigidity (Group C) to the diamine residue group suitable for improving transparency (Group D) is preferably 0.05 mol or more and 9 mol or less of the diamine residue group suitable for improving rigidity (Group C) per 1 mol of the diamine residue group suitable for improving transparency (Group D), more preferably 0.1 mol or more and 5 mol or less, and even more preferably 0.3 mol or more and 4 mol or less.
[0111] In the structures represented by the above general formula (5) and the above general formula (7), n and n' each independently represent the number of repeating units and are 1 or more. The number of repeating units in the polyimide, n, may be appropriately selected according to the structure so as to show a preferred glass transition temperature described later, and is not particularly limited. The average number of repeating units is usually 10 to 2000, and more preferably 15 to 1000.
[0112] The polyimide resin may contain a polyamide structure in part thereof, for example, a polyamideimide structure containing a tricarboxylic acid residue such as trimellitic anhydride, or a polyamide structure containing a dicarboxylic acid residue such as terephthalic acid.
[0113] From the viewpoint of heat resistance, the polyimide resin preferably has a glass transition temperature of 250° C. or higher, and more preferably 270° C. or higher. On the other hand, from the viewpoints of ease of stretching and reduction of the bake temperature, the glass transition temperature is preferably 400° C. or lower, and more preferably 380° C. or lower.
[0114] An example of a polyimide resin is a compound having a structure represented by the following chemical formula: In the following chemical formula, n is a repeating unit and represents an integer of 2 or more. [ka]
[0115] [ka]
[0116] [ka]
[0117] [ka]
[0118]
change
[0119]
change
[0120]
change
[0121]
change
[0122]
change
[0123]
change
[0124]
change
[0125]
change
[0126]
change
[0127]
change
[0128]
change
[0129] [ka]
[0130] [ka]
[0131] Among the above polyimide-based resins, polyimide-based resins or polyamide-based resins having a structure in which intramolecular or intermolecular charge transfer is unlikely to occur are preferred because they have excellent transparency. Specific examples thereof include fluorinated polyimide-based resins such as those represented by the above chemical formulas (8) to (15), and polyimide-based resins having an alicyclic structure such as those represented by the above formulas (15) to (19).
[0132] In addition, the fluorinated polyimide resins such as those represented by the above chemical formulas (8) to (15) have high heat resistance due to their fluorinated structure, and are not discolored by heat during the production of a polyimide film made of the polyimide resin, and therefore have excellent transparency.
[0133] The polyamide resin is a concept including not only aliphatic polyamides but also aromatic polyamides (aramids). Examples of polyamide resins include compounds having skeletons represented by the following chemical formulas (25) to (27). In the following formulas, n is a repeating unit and represents an integer of 2 or more.
[0134] [ka]
[0135] [ka]
[0136] [ka]
[0137] The substrate made of the polyimide-based resin or polyamide-based resin represented by the above chemical formulas (8) to (24) and (27) may be commercially available. Examples of commercially available substrates containing the polyimide-based resin include Neoprim (registered trademark) manufactured by Mitsubishi Gas Chemical Company, Inc., and examples of commercially available substrates containing the polyamide-based resin include Miktron (registered trademark) manufactured by Toray Industries, Inc.
[0138] The polyimide-based resins or polyamide-based resins represented by the above chemical formulas (8) to (24) and (27) may be synthesized by a known method. For example, a method for synthesizing the polyimide-based resin represented by the above chemical formula (8) is described in JP-A-2009-132091, and specifically, the polyimide-based resin can be obtained by reacting 4,4'-hexafluoropropylidenebisphthalic dianhydride (FPA) represented by the following chemical formula (28) with 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFDB). [ka]
[0139] The weight average molecular weight of the polyimide resin or polyamide resin is preferably in the range of 3000 to 500,000, more preferably in the range of 5000 to 300,000, and even more preferably in the range of 10,000 to 200,000. If the weight average molecular weight is less than 3000, sufficient strength may not be obtained, and if it exceeds 500,000, the viscosity increases and the solubility decreases, so that a substrate with a smooth surface and a uniform film thickness may not be obtained. In this specification, the "weight average molecular weight" is a polystyrene-equivalent value measured by gel permeation chromatography (GPC).
[0140] From the viewpoint of being able to improve the hardness, it is preferable to use a substrate made of a fluorinated polyimide resin represented by the above chemical formulas (8) to (15) or a polyamide resin having a halogen group represented by the above chemical formula (27), etc., for the resin substrate 51. Among them, from the viewpoint of being able to further improve the hardness, it is more preferable to use a substrate containing a polyimide resin represented by the above chemical formula (8).
[0141] Examples of polyester-based resins include resins containing at least one of polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate as a constituent component.
[0142] The thickness of the resin substrate 51 is preferably 10 μm or more and 100 μm or less. If the thickness of the resin substrate 51 is 10 μm or more, curling of the optical film can be suppressed, sufficient hardness can be obtained, and even if the optical film is manufactured by roll to roll, wrinkles are unlikely to occur, and there is no risk of causing deterioration of the appearance. On the other hand, if the thickness of the resin substrate 51 is 100 μm or less, the folding performance of the optical film 50 is good, the requirements of the continuous folding test can be satisfied, and it is preferable in terms of reducing the weight of the optical film 50. The thickness of the resin substrate 51 can be measured by the same method as the film thickness of the resin layer 10. The lower limit of the resin substrate 51 is more preferably 20 μm or more, 30 μm or more, or 40 μm or more, and the upper limit of the resin substrate 51 is more preferably 80 μm or less, or 50 μm or less.
[0143] <Functional layer> The functional layer 52 is similar to the functional layer 31, and therefore a description thereof will be omitted here.
[0144] <<<Method of manufacturing resin layer and optical film>>> The resin layer 10 and the optical films 30 and 50 can be produced as follows. When producing the resin layer 10 and the optical film 30, first, a resin layer composition is applied onto one surface of a release film using a coating device such as a bar coater to form a coating film.
[0145] <<Composition for resin layer>> The resin layer composition contains at least an ionizing radiation curable compound. In addition to the ionizing radiation curable compound, the resin layer composition may further contain a solvent and a polymerization initiator. The ionizing radiation curable compound has been described in the section on the resin layer 10, and therefore will not be described here.
[0146] <Solvent> Examples of the solvent include alcohols (e.g., methanol, ethanol, propanol, isopropanol, n-butanol, s-butanol, t-butanol, benzyl alcohol, PGME, ethylene glycol, and diacetone alcohol), ketones (e.g., acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, heptanone, diisobutyl ketone, diethyl ketone, and diacetone alcohol), esters (methyl acetate, ethyl acetate, butyl acetate, n-propyl acetate, isopropyl acetate, and formic acid), and Examples of the solvent include methyl, PGMEA), aliphatic hydrocarbons (e.g., hexane, cyclohexane), halogenated hydrocarbons (e.g., methylene chloride, chloroform, carbon tetrachloride), aromatic hydrocarbons (e.g., benzene, toluene, xylene), amides (e.g., dimethylformamide, dimethylacetamide, n-methylpyrrolidone), ethers (e.g., diethyl ether, dioxane, tetrahydrofuran), ether alcohols (e.g., 1-methoxy-2-propanol), carbonates (dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate), and the like. These solvents may be used alone or in combination of two or more. Among them, methyl isobutyl ketone and methyl ethyl ketone are preferred as the solvent, in that they can dissolve or disperse components such as urethane (meth)acrylate and other additives and can suitably coat the resin layer composition.
[0147] <Polymerization initiator> The polymerization initiator is a component that is decomposed by irradiation with ionizing radiation to generate radicals and initiate or advance the polymerization (crosslinking) of a polymerizable compound.
[0148] The polymerization initiator is not particularly limited as long as it can release a substance that initiates radical polymerization by irradiation with ionizing radiation. The polymerization initiator is not particularly limited, and known initiators can be used, and specific examples thereof include acetophenones, benzophenones, Michler's benzoyl benzoate, α-amyloxime ester, thioxanthones, propiophenones, benzils, benzoins, and acylphosphine oxides. It is also preferable to use a photosensitizer in combination, and specific examples thereof include n-butylamine, triethylamine, and poly-n-butylphosphine.
[0149] After forming a coating film of the resin layer composition, if the resin layer composition contains a solvent, the coating film is dried by various known methods, for example by heating at a temperature of 30°C or higher and 120°C or lower for 10 to 120 seconds, to evaporate the solvent.
[0150] After drying the coating film, the coating film is irradiated with ionizing radiation such as ultraviolet light to harden it. Then, the release film is peeled off to obtain the resin layer 10. The resin layer 10 satisfies the above-mentioned relational formula (1), and such a resin layer 10 can be obtained not only by adjusting the composition of the resin layer composition, but also by, for example, irradiating one side of the coating film with ionizing radiation and appropriately adjusting the irradiation conditions of the ionizing radiation and / or the type and amount of the polymerization initiator.
[0151] In addition, when forming the optical film 30, the coating film of the resin layer composition is dried, and then irradiated with ionizing radiation such as ultraviolet light to semi-cure the coating film. In this specification, "semi-cure" means that curing substantially proceeds when further irradiated with ionizing radiation.
[0152] Thereafter, a functional layer composition for forming the functional layer 31 is applied onto the semi-cured coating film using a coating device such as a bar coater to form a coating film of the functional layer composition.
[0153] <<Composition for functional layer>> The composition for the functional layer contains a polymerizable compound. The composition for the functional layer may further contain an ultraviolet absorber, a spectral transmittance adjuster, an antifouling agent, inorganic particles, a leveling agent, a solvent, and a polymerization initiator, as necessary. The solvent and the polymerization initiator are the same as those in the composition for the resin layer, and therefore the description thereof will be omitted here.
[0154] After forming a coating film of the composition for the functional layer, the coating film is dried by various known methods, for example by heating at a temperature of 30°C or higher and 120°C or lower for 10 to 120 seconds, to evaporate the solvent.
[0155] After drying the coating of the functional layer composition, the coating is fully cured by irradiating it with ionizing radiation such as ultraviolet light to form the functional layer 31. In this specification, "fully cured" means that the curing does not substantially proceed even if the coating is further irradiated with ionizing radiation. Thereafter, the release film is peeled off to obtain the optical film 30.
[0156] When forming the optical film 50, for example, first, the functional layer 52 is formed on one surface of the resin substrate 51. The functional layer 52 can be formed by the same method as the functional layer 31. Then, the resin layer 10 is formed in the same manner as described above on the surface of the resin substrate 51 opposite to the surface on which the functional layer 52 is formed. In this manner, the optical film 50 can be obtained.
[0157] When the resin layer has a single-layer structure composed of a soft resin layer with uniform hardness, good foldability can be obtained. However, due to the softness of the resin layer, the impact resistance is poor. On the other hand, when the resin layer has a single-layer structure composed of a hard resin layer with uniform hardness, good impact resistance can be obtained. However, due to the hardness of the resin layer, the foldability is poor. Further, when the resin layer has a multi-layer structure of a soft layer and a hard layer, there is a risk of peeling or cracking at the interface between the soft layer and the hard layer during folding, and there is also a risk of wrinkles occurring due to a difference in deformation between the soft layer and the hard layer during folding. From such findings, the inventors of the present invention have found that in order to obtain a resin layer having good foldability and good impact resistance such that the surface of the optical film does not dent when an impact is applied to the surface of the optical film and a member (for example, a polarizing plate) existing inside the optical film in the image display device is not damaged, it is necessary to gradually change the hardness from one surface to the other surface in the resin layer having a single-layer structure. According to the present embodiment, since the displacement amounts d1 to d3 in the first region 10C to the third region 10E of the resin layer 10 having a single-layer structure satisfy the relationship d1 < d2 < d3, good foldability and good impact resistance can be obtained.
[0158] <<<image display device>>> The optical film 30 can be incorporated into a foldable image display device for use. FIG. 6 is a schematic diagram of the image display device according to this embodiment. As shown in FIG. 6, the image display device 60 mainly includes a housing 61 housing a battery and the like, a display element 62, a circular polarizing plate 63, a touch sensor 64, and an optical film 30 laminated in this order toward the observer side. An adhesive layer 65 or an adhesive layer having optical transparency is disposed between the housing 61 and the display element 62, between the display element 62 and the circular polarizing plate 63, between the circular polarizing plate 63 and the touch sensor 64, and between the touch sensor 64 and the optical film 30, and these members are fixed to each other by the adhesive layer 65 or the adhesive layer. The adhesive layer 65 is disposed between the housing 61 and the display element 62, between the display element 62 and the circular polarizing plate 63, between the circular polarizing plate 63 and the touch sensor 64, and between the touch sensor 64 and the optical film 50, but the location of the adhesive layer is not particularly limited as long as it is between the optical film and the display element.
[0159] The optical film 30 is disposed so that the functional layer 31 is closer to the viewer than the resin layer 10. In the image display device 60, the surface 30A of the optical film 30 constitutes the surface 60A of the image display device 60.
[0160] In the image display device 60, the display element 62 is an organic light-emitting diode element including an organic light-emitting diode element or the like. The touch sensor 64 is disposed closer to the observer than the circular polarizer 63, but may be disposed between the display element 62 and the circular polarizer 63. The touch sensor 64 may be of an on-cell type or an in-cell type. For example, an OCA (Optical Clear Adhesive) may be used as the adhesive layer 65.
[0161] [Second embodiment] Hereinafter, an optical film and an image display device according to a second embodiment of the present invention will be described with reference to the drawings. Fig. 7 is a schematic diagram of the optical film according to this embodiment, and Fig. 8(A) and Fig. 8(B) are schematic diagrams showing the state of a folding static test.
[0162] <<<Optical films>>> The optical film 70 shown in FIG. 7 is foldable and has optical transparency. The optical film 70 has a surface 70A and a back surface 70B opposite to the surface 70A. The optical film 70 also includes a resin substrate 71, a resin layer 72, and a hard coat layer 73. In the optical film 70, the resin layer 72 is provided closer to the back surface 70B of the optical film 70 than the resin substrate 71, and the hard coat layer 73 is provided closer to the surface 70A of the optical film 70 than the resin substrate 71. Specifically, the optical film 70 includes the hard coat layer 73, the resin substrate 71, and the resin layer 72 in this order from the surface 70A toward the back surface 70B.
[0163] The optical film 70 is less likely to develop a fold even when subjected to a folding static test. The folding static test and confirmation of the fold are performed as follows. First, the optical film 70 is cut out to a size of 30 mm x 100 mm. Then, in order to reproduce the state inside the image display device, as shown in FIG. 8(A), 30 mm x 48 mm areas including side portions 70C and 70D on the two opposing short sides (30 mm) of the cut-out optical film 70 are fixed to glass plates 75 each having a size of 50 mm x 100 mm. The glass plates 75 are fixed to the back surface 70B side (resin layer 72 side) of the optical film 70. Then, the glass plates 20 are arranged parallel to each other so that the distance between the opposing sides 70C and 70D of the optical film 70 is 2.5 mm, and the optical film 70 is folded so that the front surface 70A is on the inside. In this state, it is left at 25°C for 100 hours. Thereafter, the optical film 70 is opened with the glass plate 75 still attached, and the surface of the optical film 70 is flattened as shown in Fig. 8(B) . In this state, it is visually confirmed whether the optical film 70 has a crease.
[0164] The optical film 70 is foldable in the same manner as the optical film 30. In the optical film 70, for example, even if a folding test (continuous folding test) is repeatedly performed on the optical film 70 100,000 times, it is preferable that the optical film 70 does not crack or break, even if the continuous folding test is repeatedly performed 200,000 times, it is more preferable that the optical film 70 does not crack or break, even if the continuous folding test is repeatedly performed 300,000 times, and it is most preferable that the optical film 70 does not crack or break, even if the continuous folding test is repeatedly performed 1,000,000 times. The continuous folding test is performed by the same method as the continuous folding test described in the first embodiment. It is more preferable that the optical film 70 does not crack or break, even if the continuous folding test is repeatedly performed 100,000 times with the distance φ between the two opposing sides set to 20 mm, 10 mm, 6 mm, or 3 mm. The smaller the distance between the two opposing sides, the more preferable.
[0165] In the case where another film such as a polarizing plate is provided on one side of the optical film 70 via an adhesive layer or bonding layer, the other film is peeled off together with the adhesive layer or bonding layer before performing the folding static test or folding test.
[0166] The surface 70A of the optical film 70 (surface 73A of the hard coat layer 73) preferably has a hardness (pencil hardness) of B or more, and more preferably H or more, when measured by a pencil hardness test specified in JIS K5600-5-4:1999. The pencil hardness test is carried out by the same method as the pencil hardness test described in the section of the first embodiment.
[0167] The yellow index and its measuring method of the optical film 70 are the same as the yellow index and its measuring method of the optical film 50. The haze value (total haze value), total light transmittance and their measuring methods of the optical film 70 are the same as the haze value, total light transmittance and their measuring methods of the resin layer 10. The use, size and arrangement location of the optical film 70 are the same as the use, size and arrangement location of the optical film 30.
[0168] <<Resin substrate>> The resin substrate 71 is a substrate containing a resin having optical transparency. The constituent material of the resin substrate 71 may be the same as that of the resin substrate 51. The thickness of the resin substrate 71 is 20 μm or less. If the thickness of the resin substrate 71 is 20 μm or less, the resin substrate 71 is thin, so that the resin substrate 71 is not stretched much when the optical film 70 is folded. The thickness of the resin substrate 71 can be measured by the same method as that for the film thickness of the resin layer 72. From the viewpoint of reducing the amount of stretch, the upper limit of the resin substrate 71 is more preferably 18 μm or less, 16 μm or less, or 14 μm or less. Moreover, from the viewpoint of ensuring a desired pencil hardness, the lower limit of the resin substrate 71 is preferably 2 μm or more, 4 μm or more, or 6 μm or more.
[0169] The film thickness of the resin substrate 71 is determined by photographing a cross section of the resin substrate 71 using a scanning transmission electron microscope (STEM) in a manner similar to that used to photograph the cross section of the functional layer 31, measuring the film thickness of the resin substrate 71 at 10 points on the image of the cross section, and calculating the arithmetic average of the film thicknesses at the 10 points.
[0170] When a Berkovich indenter is pressed into the cross section of the resin substrate 71 in the thickness direction with a maximum load of 200 μN, the displacement d4 of the resin substrate 71 is 50 nm or more and 250 nm or less. If the displacement d4 of the resin substrate 71 is 50 nm or more, good flexibility can be obtained, and if it is 250 nm or less, the desired pencil hardness can be ensured. From the viewpoint of obtaining excellent flexibility, the lower limit of the displacement d4 of the resin substrate 71 is preferably 80 nm or more, 100 nm or more, or 110 nm or more. Moreover, from the viewpoint of further ensuring the desired pencil hardness, the upper limit of the displacement d4 of the resin substrate 71 is more preferably 220 nm or less, 200 nm or less, or 180 nm or less. The method for measuring the displacement d4 of the resin substrate 71 is the same as the method for measuring the displacements d1 to d3 of the resin layer 10. In addition, the Berkovich indenter is pressed into portions of the cross section of the resin substrate 71 in the thickness direction, at least 500 nm away from each of both side ends toward the center of the resin substrate, in order to avoid the influence of the side edges of the resin substrate.
[0171] <<Resin layer>> The resin layer 72 is a layer that contains a resin having optical transparency and has impact absorbing properties. The resin layer 72 is provided on the first surface 71A side of the resin substrate 71. In the optical film 70 of FIG.
[0172] The thickness of the resin layer 72 is 50 μm or more. If the thickness of the resin layer 72 is 50 μm or more, good impact resistance can be obtained. The lower limit of the thickness of the resin layer 72 is more preferably 60 μm or more, 65 μm or more, or 70 μm or more. The upper limit of the thickness of the resin layer 72 is more preferably 120 μm or less, 110 μm or less, or 100 μm or less, from the viewpoint of achieving a thin film and good processability. The thickness of the resin layer 72 is measured by the same method as that of the resin substrate 71.
[0173] The ratio of the thickness of the resin layer 72 to the thickness of the resin substrate 71 (thickness of the resin layer 72 / thickness of the resin substrate 71) is 4.0 or more and 12.0 or less. If this ratio is 4.0 or more, it is possible to achieve both suppression of folding habits and impact resistance. Furthermore, if this ratio is 12.0 or less, it is possible to ensure a desired pencil hardness. From the viewpoint of obtaining excellent suppression of folding habits and excellent impact resistance, the lower limit of this ratio is more preferably 4.5 or more, 5.0 or more, or 6.0 or more, and from the viewpoint of obtaining excellent flexibility, the upper limit is preferably 11.0 or less, 10.0 or less, or 8.0 or less.
[0174] When a Berkovich indenter is pressed into the cross section of the resin layer 72 in the thickness direction with a maximum load of 200 μN, the displacement d5 of the resin layer 72 is 200 nm or more and 1500 nm or less. If the displacement d5 of the resin layer 72 is 200 nm or more, the desired flexibility can be ensured, and if it is 1500 nm or less, the impact resistance required for the impact resistance test described later can be ensured. The lower limit of the displacement d5 of the resin layer 72 is preferably 300 nm or more, 400 nm or more, or 500 nm or more in order to further suppress the protrusion of the resin layer 72 when folded. In addition, the upper limit of the displacement d5 of the resin layer 72 is more preferably 1400 nm or less, 1200 nm or less, or 1100 nm or less in order to obtain excellent impact resistance. The resin layer of this embodiment is softer than the resin substrate and the hard coat layer and is more affected by viscosity, so the method of measuring the indentation hardness by the nanoindentation method was not suitable. Therefore, the displacement amount is used as an index of hardness. The displacement amount d5 of the resin layer 72 is measured by the same method as the displacement amount d4 of the resin base material 71.
[0175] The ratio of the displacement d5 to the displacement d4 (d5 / d4) is preferably 1.5 or more. If d5 / d4 is 1.5 or more, it is possible to achieve both bending habit suppression and impact resistance. In addition, the lower limit of d5 / d4 is more preferably 2.0 or more, 2.5 or more, or 3.0 or more from the viewpoint of obtaining excellent bending habit suppression and excellent impact resistance, and the upper limit is preferably 10.0 or less, 7.0 or less, or 5.0 or less from the viewpoint of ensuring the desired flexibility.
[0176] The resin constituting the resin layer 72 is not particularly limited as long as it is a resin with a displacement d5 of 200 nm or more and 1500 nm or less. Examples of such resins include cured products (polymerized products) of ionizing radiation curable compounds (ionizing radiation polymerizable compounds). Examples of cured products of ionizing radiation curable compounds include urethane resins and acrylic gels. The term "gel" generally refers to a dispersion system that is highly viscous and has lost fluidity.
[0177] (Urethane resin) The urethane-based resin is the same as the urethane-based resin described in the section for the resin layer 10 .
[0178] (Acrylic gel) As the acrylic gel, various types of polymers obtained by polymerizing a monomer containing an acrylic acid ester, which are used in adhesives, etc., can be used. Specifically, examples of acrylic gels that can be used include polymerized or copolymerized acrylic monomers such as ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-hexyl (meth)acrylate, n-amyl (meth)acrylate, i-amyl (meth)acrylate, octyl (meth)acrylate, i-octyl (meth)acrylate, i-myristyl (meth)acrylate, lauryl (meth)acrylate, nonyl (meth)acrylate, i-nonyl (meth)acrylate, i-decyl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, and i-stearyl (meth)acrylate. In this specification, the term "(meth)acrylate" includes both "acrylate" and "methacrylate." The acrylic acid ester used in the (co)polymerization may be used alone or in combination of two or more kinds.
[0179] <<Hard coat layer>> The hard coat layer 73 is provided on the second surface 71B side of the resin substrate 71. In the optical film 70 of Fig. 7, the hard coat layer 73 is adjacent to the second surface 11B of the resin substrate 11. The "hard coat layer" in this embodiment refers to a layer having a pencil hardness of "H" or more in the above-mentioned pencil hardness test.
[0180] When a Berkovich indenter is pressed into the cross section of the hard coat layer 73 in the thickness direction with a maximum load of 500 μN, the displacement d6 of the hard coat layer 73 is preferably 500 nm or less. If the displacement d6 of the hard coat layer 73 is 500 nm or less, the desired pencil hardness can be ensured. From the viewpoint of ensuring flexibility, the lower limit of the displacement d6 of the hard coat layer 73 is preferably 50 nm or more, 60 nm or more, or 70 nm or more. Moreover, the upper limit of the displacement d6 of the hard coat layer 73 is more preferably 500 nm or less, 490 nm or less, or 480 nm or less. The displacement d6 of the hard coat layer 73 is measured by the same method as the displacement d4 of the resin substrate 71. The measurement conditions are as follows. (Measurement conditions) Control method: Load control (maximum load 500μN) Lift amount: 0nm Preload: 0.5μN ·Loading speed: 20μN / sec ·Holding time: 5 seconds ·Loading and unloading speed: 20μN / sec ·Measurement temperature: 23±5℃ Relative humidity: 30%~70%
[0181] The thickness of the hard coat layer 73 is preferably 3 μm or more and 10 μm or less. If the thickness of the hard coat layer 73 is 3 μm or more, good hardness can be obtained, and if it is 10 μm or less, deterioration of processability can be suppressed. In this specification, the "thickness of the hard coat layer" means the thickness (total thickness) of the hard coat layer when the hard coat layer has a multi-layer structure. The lower limit of the thickness of the hard coat layer 73 is more preferably 5 μm or more, and the upper limit is more preferably 8 μm or less. The thickness of the hard coat layer 73 is measured by the same method as that of the resin substrate 71.
[0182] The hard coat layer 73 preferably further contains a resin and inorganic particles dispersed in the resin. The resin and inorganic particles of the hard coat layer 73 are the same as those described in the functional layer 31 section.
[0183] The hard coat layer 73 may contain materials other than those mentioned above as long as the above-mentioned displacement amount is satisfied, and may contain, for example, a polymerizable monomer or a polymerizable oligomer that forms a cured product by irradiation with ionizing radiation as a resin component material. The polymerizable monomer and the polymerizable oligomer are the same as those described in the section of the functional layer 31.
[0184] <<<Optical film manufacturing method>>> The optical film 70 can be produced as follows: First, a composition for a hard coat layer is applied onto the second surface 71B of the resin substrate 71 using a coating device such as a bar coater to form a coating film of the composition for a hard coat layer.
[0185] <Hard Coat Layer Composition> The composition for hard coat layer contains a polymerizable compound. The composition for hard coat layer may contain, as necessary, an ultraviolet absorber, a spectral transmittance adjuster, an antifouling agent, inorganic particles, a leveling agent, a solvent, and a polymerization initiator. The solvent and the polymerization initiator are the same as those described in the column for the composition for resin layer of the first embodiment.
[0186] After forming a coating film of the composition for a hard coat layer, the coating film is dried by various known methods, for example, by heating at a temperature of 30° C. or higher and 120° C. or lower for 10 to 120 seconds, to evaporate the solvent.
[0187] After the coating of the composition for hard coat layer is dried, the coating is cured by irradiating it with ionizing radiation such as ultraviolet light, thereby forming the hard coat layer 73 .
[0188] After forming the hard coat layer 73, a resin layer composition for forming the resin layer 72 is applied to the first surface 71A of the resin substrate 71 by a coating device such as a bar coater to form a coating film of the resin layer composition. Then, the coating film is cured to form the resin layer 72.
[0189] <Composition for resin layer> When the resin layer 72 is made of a urethane-based resin, for example, the ionizing radiation curable urethane-based resin composition described above in the section on urethane-based resins can be used as the resin layer composition.
[0190] After forming a coating film of the resin layer composition, if the resin layer composition contains a solvent, the coating film is dried by various known methods, for example by heating at a temperature of 30°C or higher and 120°C or lower for 10 to 120 seconds, to evaporate the solvent.
[0191] After drying the coating, the coating is irradiated with ionizing radiation such as ultraviolet light to harden it, thereby forming the resin layer 12 and obtaining the optical film 70.
[0192] It is believed that the folding habit occurs when the inner or outer surface of the resin substrate is stretched when the optical film is folded, causing the resin substrate to exceed its elastic limit and undergo plastic deformation. Therefore, if the resin substrate is made thin, the stretching of the resin substrate can be suppressed when the optical film is folded. However, if the resin substrate is made thin, the impact resistance decreases. On the other hand, a resin layer with a displacement of 200 nm or more and 1500 nm or less when an indentation test is performed has a wider elastic region than the resin substrate, so that it is less likely to undergo plastic deformation and to develop a folding habit than the resin substrate. In addition, if the thickness of such a resin layer is thin, the impact resistance decreases, so a certain thickness is required to obtain good impact resistance such that the surface of the optical film does not become dented when an impact is applied to the surface of the optical film. In contrast, according to the present embodiment, a resin layer 72 having a displacement d5 of 200 nm or more and 1500 nm or less when an indentation test is performed is provided on the first surface 71A side of the resin substrate 71, which has a thickness of 20 μm or less and a displacement d4 of 50 nm or more and 250 nm or less when an indentation test is performed. The thickness of the resin substrate 71 is 20 μm or less, the film thickness of the resin layer 72 is 50 μm or more, and the ratio of the film thickness of the resin layer 72 to the thickness of the resin substrate 71 is 4.0 or more and 12.0 or less. As a result, the optical film 70 is less likely to develop a fold when folded, and good impact resistance can be obtained.
[0193] <<<Image display devices>>> The optical film 70 can be incorporated into a foldable image display device. The structure of the image display device incorporating the optical film 70 is similar to the structure of the image display device 60, except that the optical film 70 is incorporated instead of the optical film 30.
[0194] [Third embodiment] Hereinafter, an optical film and an image display device according to a third embodiment of the present invention will be described with reference to the drawings. Fig. 9 is a schematic diagram of the optical film according to this embodiment, Fig. 10 is a partially enlarged view of the optical film in Fig. 9, and Fig. 11 is a schematic diagram of another optical film according to this embodiment.
[0195] <<<Optical films>>> An optical film 80 shown in FIG. 9 is used in an image display device and is foldable.
[0196] As shown in FIG. 9, the optical film 80 includes a resin substrate 81 and a resin layer 82 provided on a first surface 81A side, which is one surface of the resin substrate 81. The optical film 80 further includes a functional layer 85 provided on a surface 82A of the resin layer 82. The "resin layer" in this embodiment is a layer containing a resin, and may have a single-layer structure or a multi-layer structure of two or more layers. The resin layer 82 has a multi-layer structure of two or more layers, specifically a two-layer structure, as described below, but may also have a single-layer structure. The functional layer 85 has a single-layer structure, but may also have a multi-layer structure of two or more layers.
[0197] 9, the surface 80A of the optical film 80 is a surface having projections and recesses. In FIG. 9, the surface 80A of the optical film 80 is a surface 85A of the functional layer 85. The back surface 80B of the optical film 80 is a second surface 81B of the resin base material 81, which is opposite to the first surface 81A.
[0198] The optical film 80 is foldable in the same manner as the optical film 30. In the optical film 80, for example, even if a folding test (continuous folding test) is repeatedly performed on the optical film 80 100,000 times, it is preferable that no cracks or breaks occur in the optical film 80, even if the continuous folding test is repeatedly performed 200,000 times, it is more preferable that no cracks or breaks occur in the optical film 80, even if the continuous folding test is repeatedly performed 300,000 times, and it is most preferable that no cracks or breaks occur in the optical film 80, even if the continuous folding test is repeatedly performed 1,000,000 times. The continuous folding test is performed in the same manner as the continuous folding test described in the first embodiment, except that the distance φ between the two opposing sides is 8 mm. It is further preferable that the optical film 80 does not crack or break even when a continuous folding test is repeated 100,000 times with the distance φ between the two opposing sides being 6 mm, 4 mm, or 2 mm.
[0199] The surface 80A of the optical film 80 (the surface 85A of the functional layer 85) was coated with #0000 steel wool (product name "Bonstar", manufactured by Japan Steel Wool Co., Ltd.) at 1 kgf / cm 2 It is preferable that no scratches are generated when a scratch resistance test is performed in which the optical film is rubbed back and forth 10 times at a speed of 60 mm / sec while applying a load of 100 mm. The test is performed in an environment of a temperature of 23±5°C and a relative humidity of 30% to 70%, with an optical film cut into a size of 50 mm×100 mm fixed on a glass plate with Cellotape (registered trademark) manufactured by Nichiban Co., Ltd. so that the surface of the optical film faces up without bending or wrinkling. The scratches are those that are visually recognized under a three-wavelength fluorescent lamp after black vinyl tape (black vinyl tape NO200-38-21 manufactured by Yamato Co., Ltd.) is attached to the glass surface opposite the optical film.
[0200] The yellow index and its measuring method of the optical film 80 are similar to the yellow index and its measuring method of the optical film 50. The total light transmittance and its measuring method of the optical film 80 are similar to the total light transmittance and its measuring method of the resin layer 10. The use, size and arrangement location of the optical film 80 are similar to the use, size and arrangement location of the optical film 30.
[0201] The haze value (total haze value) of the optical film 80 is preferably 20% or less. If the haze value of the optical film 80 is 20% or less, whitening of the image display surface can be suppressed when the optical film 80 is used in a mobile terminal. The lower limit of the haze value may be 1% or more, and the upper limit is more preferably 15% or less, 10% or less, or 5% or less. The method for measuring the haze value of the optical film 80 is the same as the method for measuring the haze value of the resin layer 10.
[0202] The optical film 80 preferably has a transmitted image clarity of 40% or more and 90% or less at a 0.125 mm comb (comb A), and 80% or more at a 2.0 mm comb (comb B). If the transmitted image clarity at a 0.125 mm comb (comb A) is 40% or more, glare (sparkle) can be suppressed, and if the transmitted image clarity at a 0.125 mm comb (comb A) is 90% or less, the pressure mark can be made less noticeable. If the transmitted image clarity at a 2.0 mm comb (comb B) is 80% or more, the image can be clearly viewed. The lower limit of the transmitted image clarity at the 0.125 mm comb (comb A) is more preferably 45% or more, 50% or more, or 55% or more, and the upper limit is more preferably 85% or less. The lower limit of the transmitted image clarity at the 2.0 mm comb (comb B) is more preferably 90% or more.
[0203] The above-mentioned transmitted image clarity can be measured in an environment of 23±5°C temperature and 30% to 70% relative humidity using an image clarity measuring instrument (for example, product name "ICM-IT", manufactured by Suga Test Instruments Co., Ltd.) according to a method conforming to the transmission method of image clarity of JIS K7374:2007. The above-mentioned transmitted image clarity is measured by cutting the optical film into a size of 50 mm x 100 mm, and then placing the resin substrate on the light source side in an image clarity measuring instrument set for transmission measurement in a state without curls or wrinkles and without fingerprints or dust, and measuring three times for one optical comb, and taking the arithmetic average value of the values obtained by the three measurements. Note that if the optical film cannot be cut into the above-mentioned size, for example, since the opening of the sample stage for measurement in ICM-1T is 25 mmφ, a sample size of 26 mm or more is required. For this reason, the optical film may be appropriately cut into a size of 27 mm x 27 mm or more. If the size of the optical film is small, the measurement points are set to three by shifting the light source little by little within the range in which the light source spot does not shift, or by changing the angle.
[0204] Surface 80A of optical film 80 is an uneven surface. The unevenness constituting surface 80A of optical film 80 preferably satisfies the following relationship when the average interval is Sm, the average tilt angle is θa, the arithmetic mean roughness is Ra, and the maximum height roughness is Ry. 0.15mm≦Sm≦0.5mm 0.02°≦θa≦0.50° 0.01μm≦Ra≦0.15μm 0.10μm≦Ry≦0.50μm
[0205] When the average interval Sm is 0.15 mm or more, the cloudiness of the image can be suppressed, and when Sm is 0.5 mm or less, glare (sparkle) can be suppressed. The lower limit of Sm is more preferably 0.20 mm or more or 0.22 mm or more, and the upper limit is more preferably 0.45 mm or less or 0.40 mm or less.
[0206] If the average inclination angle θa is 0.02° or more, the pressure mark can be made less noticeable, and if θa is 0.05° or less, the cloudiness of the image can be suppressed. The lower limit of θa is more preferably 0.04° or more or 0.06° or more, and the upper limit is more preferably 0.30° or less or 0.20° or less.
[0207] The arithmetic mean roughness Ra is preferably 0.01 μm or more and 0.15 μm or less. If Ra is 0.01 μm or more, the pressure mark can be made less noticeable, and if Ra is 0.15 μm or less, the visibility of the image can be improved. The lower limit of Ra is more preferably 0.03 μm or more or 0.05 μm or more, and the upper limit is more preferably 0.12 μm or less or 0.10 μm or less.
[0208] The maximum height roughness Ry is preferably 0.10 μm or more and 0.80 μm or less. If Ry is 0.10 μm or more, the pressure mark can be made less noticeable, and if Ry is 0.50 μm or less, glare (sparkle) can be suppressed. The lower limit of Ry is more preferably 0.15 μm or more or 0.20 μm or more, and the upper limit is more preferably 0.60 μm or less or 0.40 μm or less.
[0209] The definitions of "Sm", "Ra" and "Ry" above are as per JIS B0601:1994. The definition of "θa" is as per the instruction manual (revised on 1995.07.20) of the surface roughness measuring instrument Surfcorder SE-3400 (manufactured by Kosaka Laboratory Co., Ltd.). θa is expressed by the following formula (A). θa=tan -1 Δa …(A) In formula (A), Δa represents the slope as an aspect ratio, and is the sum of the differences between the minimum and maximum parts of each concavo-convex portion (corresponding to the height of each convex portion) divided by the reference length.
[0210] Sm, Ra, Ry and θa can all be measured using, for example, a Surfcorder SE-3400, SE-3500, or SE-500 (all manufactured by Kosaka Laboratory Co., Ltd.). Even if θa cannot be measured directly, if Δa can be measured, it is possible to measure Δa and obtain θa from the measured Δa, since θa and Δa have the relationship shown in the above formula (A). The cutoff wavelength for measuring Sm, etc. is set to 0.8 mm in all cases.
[0211] When another film such as a polarizing plate is provided on the surface side of the optical film 80 via an adhesive layer or bonding layer, the other film is peeled off together with the adhesive layer or bonding layer before performing a folding test, yellow index measurement, total light transmittance measurement, haze value measurement, transmitted image clarity, average spacing Sm, etc.
[0212] The resin substrate 81 is a substrate containing a resin having optical transparency. The material of the resin substrate 81 is the same as that of the resin substrate 51. The thickness of the resin substrate 81 is preferably 10 μm or more and 100 μm or less. If the thickness of the resin substrate 81 is 10 μm or more, curling of the optical film can be suppressed, sufficient hardness can be obtained, and even if the optical film 80 is manufactured by roll to roll, wrinkles are unlikely to occur, and there is no risk of causing deterioration of the appearance. On the other hand, if the thickness of the resin substrate 81 is 100 μm or less, the folding performance of the optical film 80 is good, the requirements of the continuous folding test can be satisfied, and it is preferable in terms of reducing the weight of the optical film 80. The thickness of the resin substrate 81 is determined by photographing a cross section of the resin substrate 81 using a scanning electron microscope (SEM), measuring the film thickness of the resin substrate 81 at 10 points on the image of the cross section, and calculating the arithmetic average value of the film thicknesses at the 10 points. The lower limit of the resin base material 81 is more preferably 25 μm or more, 30 μm or more, or 35 μm or more, and the upper limit of the resin base material 81 is more preferably 80 μm or less, 75 μm or less, or 70 μm or less.
[0213] <<Resin layer>> Resin layer 82 has an uneven surface 82A. This is due to organic particles 83B, which will be described later. It is preferable that Sm, θa, Ry, and Rz of the unevenness that constitutes surface 82A are in the same range as Sm, θa, Ry, and Rz of the unevenness that constitutes surface 80A. Sm, etc. of the unevenness that constitutes surface 82A can be measured by the same method as Sm, etc. of the unevenness that constitutes surface 80A.
[0214] The resin layer 82 is a layer that functions as a hard coat layer. The resin layer 82 may have a function other than the hard coat property in addition to the hard coat property. In the present embodiment, the "hard coat layer" refers to a layer having an indentation hardness (H IT ) is 150 MPa or more. In this specification, "indentation hardness" is a value obtained from a load-displacement curve from loading to unloading of an indenter. The indentation hardness is the arithmetic average value of values obtained by measuring at 10 points. The method for measuring the indentation hardness is described in detail below.
[0215] It is preferable that the indentation hardness of the lower portion 82B of the resin layer 82 is smaller than the indentation hardness of the upper portion 82C of the resin layer 82. If the indentation hardness of the lower portion 82B of the resin layer 82 is smaller than the indentation hardness of the upper portion 82C of the resin layer 82, the organic particles 83B described below are present in the soft portion of the resin layer 82, making the optical film 80 less likely to crack when folded, and since a harder portion is present on the surface 82A side of the organic particles 83B, a superior surface hardness can be obtained.
[0216] The indentation hardness (H IT) is measured on a measurement sample using a TI950 TriboIndenter manufactured by BRUKER. Specifically, first, a block is prepared by embedding an optical film cut to 1 mm×10 mm in an embedding resin, and a uniform slice having a thickness of 70 nm to 100 nm without holes is cut out from this block by a general slice preparation method. For example, an ultramicrotome EM UC7 manufactured by Leica Microsystems can be used to prepare the slice. The remaining block from which the uniform slice without holes is cut out is used as the measurement sample. Next, in the cross section obtained by cutting out the slice in such a measurement sample, a Berkovich indenter (triangular pyramid, TI-0039 manufactured by BRUKER) is pressed vertically into the lower cross section of the resin layer for 10 seconds under the following measurement conditions up to a maximum pressing load of 50 μN. Here, the Berkovich indenter is pressed into a portion of the lower part of the resin layer, which is 500 nm away from the interface between the resin substrate and the resin layer toward the center of the resin layer, and 500 nm or more away from each of the two ends of the resin layer toward the center of the resin layer, in order to avoid the influence of the resin substrate and the side edges of the resin layer. After that, the load is held for 5 seconds and then removed over 10 seconds. max and the contact projection area A p Using and, P max / A p The indentation hardness (H IT The above contact projected area is the contact projected area corrected for the indenter tip curvature by the Oliver-Pharr method using a standard sample of fused quartz (5-0098 manufactured by BRUKER). Indentation hardness (H IT) is the arithmetic average of the values obtained by measuring at 10 points. If any of the measured values deviate from the arithmetic average by ±20% or more, that measured value shall be excluded and remeasured. Whether or not any of the measured values deviate from the arithmetic average by ±20% or more shall be determined by whether the value (%) calculated by (AB) / B×100, where A is the measured value and B is the arithmetic average, is ±20% or more. The indentation hardness of the upper part of the resin layer shall be measured in the same manner as the indentation hardness of the lower part of the resin layer, but in this case, the Berkovich indenter shall be pressed into a portion of the upper part of the resin layer, 500 nm away from the interface between the resin layer and the functional layer toward the center of the resin layer, and 500 nm or more away from each of the two ends of the resin layer toward the center of the resin layer, in order to avoid the influence of the functional layer and the side edges of the resin layer. (Measurement conditions) Control method: Load control method ·Loading speed: 5μN / sec ·Holding time: 5 seconds ·Loading and unloading speed: 5μN / sec ·Temperature: 23℃~25℃ Relative humidity: 30%~70%
[0217] The thickness of the resin layer 82 is preferably 2 μm or more and 15 μm or less. If the thickness of the resin layer 82 is 2 μm or more, sufficient hardness as a hard coat layer can be obtained, and if the thickness is 15 μm or less, deterioration of processability can be suppressed. In this embodiment, the "thickness of the resin layer" means the thickness (total thickness) of the resin layer, when the resin layer has a multi-layer structure. The lower limit of the resin layer 82 is more preferably 3 μm or more, 4 μm or more, or 5 μm or more, and the upper limit of the resin layer 82 is more preferably 12 μm or less, 10 μm or less, or 8 μm or less.
[0218] The thickness of the resin layer 82 is determined by photographing a cross section of the resin layer 12 using a scanning transmission electron microscope (STEM) or a transmission electron microscope (TEM) in a manner similar to that for photographing a cross section of the functional layer 31, measuring the thickness of the resin layer 82 at 10 points on the image of the cross section, and calculating the arithmetic average value of the thicknesses at the 10 points. Note that, although a mixed layer containing the components constituting the resin substrate 81 and the components constituting the resin layer 82 may exist between the resin substrate 81 and the resin layer 82, the thickness of the mixed layer is not included in the thickness of the resin layer.
[0219] The resin layer 82 contains organic particles 83B, which will be described later. The organic particles 83B are unevenly distributed on the resin base material 81 side from a center line CL (see FIG. 10), which is a virtual line that bisects the resin layer 82 in the thickness direction D2 of the resin layer 82. Whether the organic particles 83B are unevenly distributed on the resin base material 81 side from the center line CL can be determined by obtaining the center of each organic particle 83B from a cross-sectional photograph of the resin layer 12 taken with a scanning transmission electron microscope (STEM) or a transmission electron microscope (TEM), and determining whether the average position of the centers is located on the resin base material 81 side from the center line CL. Specifically, first, similar to the measurement of the thickness of the resin layer 82, a cross section of the resin layer 82 is photographed using a scanning transmission electron microscope (STEM) or a transmission electron microscope (TEM) to prepare cross-sectional photographs at 10 locations. In each cross-sectional photograph, the thickness of the resin layer 82 is measured, and the position of the center line CL is determined in each cross-sectional photograph. In addition, the center of the organic particles 83B appearing in each cross-sectional photograph is determined. The center can be found by finding the midpoint of a virtual line segment connecting the closest point of the organic particle to the resin substrate in the thickness direction of the resin layer and the farthest point. Then, the distance between the center of the organic particle 83B and the center line CL is measured for each organic particle 83B in each cross-sectional photograph. At this time, the distance between the center of the organic particle 83B and the center line CL when the center of the organic particle 83B is located below the center line CL (on the resin substrate 81 side) is set to "-", and the distance between the center of the organic particle 83B and the center line CL when the center of the organic particle 83B is located above the center line CL (on the functional layer 85 side) is set to "+". Then, the average position of the center of the organic particle 83B can be found by finding the average of these distances, and whether or not the organic particle 83B is present on the resin substrate 81 side of the center line CL is determined depending on whether the found average position is "-" or "+".
[0220] The ratio of the average particle diameter of the organic particles 83B to the film thickness of the resin layer 82 (average particle diameter / film thickness) is preferably 0.1 or more and 1 or less. If this ratio is 0.1 or more, a desired unevenness can be imparted, and if it is 1 or less, the organic particles 83B can be easily unevenly distributed on the resin base material 11 side from the center line CL that bisects the resin layer 82 in the film thickness direction D2. The average particle diameter of the organic particles 83B is determined by measuring the particle diameters of 20 organic particles from an image of the cross section of the organic particles taken at a magnification of 5,000 times to 20,000 times using a transmission electron microscope (TEM) or a scanning transmission electron microscope (STEM), and calculating the arithmetic average value of the particle diameters of the 20 organic particles. The particle diameter of the organic particles is measured as follows. First, the major axis and the minor axis are measured, and the particle diameter of each particle is calculated from the average of the major axis and the minor axis. Here, the major axis is the longest diameter on the screen of each particle. The minor axis is determined by drawing a line segment perpendicular to the midpoint of the line segment constituting the major axis and measuring the distance between the two points where the perpendicular line segment intersects with the particle.
[0221] The resin layer 82 includes a first resin layer 83 and a second resin layer 84 provided on the surface 82A side of the first resin layer 83. In FIG. 10, the first resin layer 83 and the second resin layer 84 have the same thickness, so that the center line CL exists near the interface between the first resin layer 83 and the second resin layer 84.
[0222] <First resin layer> The first resin layer 83 contains a binder resin 83A and organic particles 83B. By including the organic particles 83B in the first resin layer 83, the surface 82A of the resin layer 82 can be made into an uneven surface. The first resin layer 83 preferably further contains inorganic particles 83C. By including the inorganic particles 83C in the first resin layer 83, it is easy to control the uneven shape. In addition to the binder resin 83A, the first resin layer 83 may contain additives such as ultraviolet absorbers, adhesion improvers, leveling agents, thixotropy-imparting agents, coupling agents, plasticizers, defoamers, fillers, and colorants as necessary, within a range that does not impair the effects of the present invention.
[0223] The indentation hardness of the first resin layer 83 is preferably smaller than that of the second resin layer 84. If the indentation hardness of the first resin layer 83 is smaller than that of the second resin layer 84, the organic particles 83B are present in the soft first resin layer 83, so that the optical film 80 is less likely to crack when folded, and the harder second resin layer 84 is present closer to the surface 82A than the organic particles 83B, so that a superior surface hardness can be obtained.
[0224] The indentation hardness of the first resin layer 83 is preferably 150 MPa or more and 350 MPa or less. If the indentation hardness of the first resin layer 83 is 150 MPa or more, a good pencil hardness can be obtained, and if the indentation hardness of the first resin layer 83 is 350 MPa or less, a good bending property can be obtained. The lower limit of the indentation hardness of the first resin layer 83 is more preferably 180 MPa or more, 200 MPa or more, or 220 MPa or more, and the upper limit is more preferably 330 MPa or less, 300 MPa or less, or 280 MPa or less. The indentation hardness of the first resin layer 83 is measured by the same method and under the same measurement conditions as the indentation hardness of the lower part 82B of the resin layer 82.
[0225] (binder resin) The binder resin 83A contains a polymer (cured product) of a polymerizable compound (curable compound). The polymerizable compound has at least one polymerizable functional group in the molecule. The polymerizable functional group and the polymerizable compound are the same as those described in the section of the functional layer 31.
[0226] (organic particles) The organic particles 83B are particles mainly composed of organic components. In addition to organic components, the organic particles 83B may contain inorganic components mixed therein. Examples of organic particles include polymethyl methacrylate particles, polyacrylic-styrene copolymer particles, melamine resin particles, polycarbonate particles, polystyrene particles, crosslinked polystyrene particles, polyvinyl chloride particles, benzoguanamine-melamine formaldehyde particles, silicone particles, fluorine-based resin particles, and polyester-based resin particles.
[0227] The organic particles 83B are preferably spherical in order to facilitate control to form the above-mentioned uneven shape. In this specification, the term "spherical" includes, for example, a perfect sphere, an elliptical sphere, and the like, but does not include so-called amorphous shapes.
[0228] The average particle size of the organic particles 83B is preferably 0.5 μm or more and 10 μm or less. If the average particle size of the organic particles 83B is within this range, it is easy to control the desired uneven shape. The lower limit of the average particle size of the organic particles is preferably 1.0 μm or more or 1.5 μm or more, and the upper limit is preferably 8 μm or less, 6 μm or less, or 4 μm or less.
[0229] (Inorganic particles) The inorganic particles 83C are particles mainly containing inorganic components. The average particle diameter of the inorganic particles 83C is preferably 1 nm or more and 50 nm or less. If the average particle diameter of the inorganic particles 83C is 1 nm or more, it is easy to control the uneven shape, and if the average particle diameter of the inorganic particles 83C is 50 nm or less, it is possible to suppress the diffusion of light by the inorganic particles 83C, and excellent contrast can be obtained. The lower limit of the average particle diameter of the inorganic particles 83C is preferably 3 nm or more, 5 nm or more, or 7 nm or more, and the upper limit is preferably 40 nm or less, 30 nm or less, or 20 nm or less. The average particle diameter of the inorganic particles 83C is determined by measuring the particle diameters of 20 inorganic particles from an image of the cross section of the inorganic particles taken at a magnification of 50,000 times to 200,000 times using a transmission electron microscope (TEM) or a scanning transmission electron microscope (STEM), and taking the arithmetic average value of the particle diameters of the 20 inorganic particles.
[0230] The content of inorganic particles 83C in the first resin layer 83 is less than the content of inorganic particles 84B (described later) in the second resin layer 84. By making the content of inorganic particles 83C less than the content of inorganic particles 84B, the first resin layer 83 can be made softer than the second resin layer 84.
[0231] The inorganic particles 83C are not particularly limited, but examples thereof include inorganic oxide particles such as silica (SiO2) fine particles, alumina particles, titania particles, tin oxide particles, antimony-doped tin oxide (abbreviated as ATO) particles, and zinc oxide particles.
[0232] When silica particles are used as the inorganic particles 83C, fumed silica particles are preferred among the silica particles from the viewpoint of easily forming a resin layer 82 having a smooth uneven surface. Fumed silica is amorphous silica having a particle size of 200 nm or less produced by a dry method, and can be obtained by reacting a volatile compound containing silicon in a gas phase. Specifically, for example, it can be produced by hydrolyzing a silicon compound such as silicon tetrachloride (SiCl4) in a flame of oxygen and hydrogen. Commercially available products of fumed silica particles include AEROSIL (registered trademark) R805 manufactured by Nippon Aerosil Co., Ltd.
[0233] When inorganic oxide particles are used as the inorganic particles 83C, the inorganic oxide particles are preferably amorphous. This is because, if the inorganic oxide particles are crystalline, the Lewis acid salt of the inorganic oxide particles may become strong due to lattice defects contained in the crystal structure, and excessive aggregation of the inorganic oxide particles may become uncontrollable.
[0234] In addition, when fumed silica particles are used as the inorganic particles 83C, there are fumed silica particles that exhibit hydrophilicity and those that exhibit hydrophobicity, and among these, those that exhibit hydrophobicity are preferred from the viewpoint of reducing the amount of moisture absorption and facilitating dispersion in the resin layer composition. Hydrophobic fumed silica can be obtained by chemically reacting the above-mentioned surface treatment agent with the silanol groups present on the surface of the fumed silica particles.
[0235] The inorganic particles 83C preferably have a spherical shape in the state of a single particle. When the inorganic particles 83C have such a spherical shape as a single particle, an image with better contrast can be obtained when the optical film is placed on the image display surface of an image display device.
[0236] <Second resin layer> The second resin layer 84 contains a binder resin 84A and inorganic particles 84B. The second resin layer 84 contains inorganic particles 84B, which can improve the hardness of the resin layer 82. The second resin layer 84 does not contain organic particles. In addition to the binder resin 84A, the second resin layer 84 may contain additives such as an ultraviolet absorber, an adhesion improver, a leveling agent, a thixotropy imparting agent, a coupling agent, a plasticizer, an antifoaming agent, a filler, and a colorant, as necessary, within a range that does not impair the effects of the present invention.
[0237] The indentation hardness of the second resin layer 84 is preferably 250 MPa or more and 450 MPa or less. If the indentation hardness of the second resin layer 84 is 250 MPa or more, good pencil hardness and scratch resistance can be obtained, and if the indentation hardness of the second resin layer 84 is 450 MPa or less, good bending properties can be obtained. The lower limit of the indentation hardness of the second resin layer 84 is more preferably 270 MPa or more, 300 MPa or more, or 320 MPa or more, and the upper limit is more preferably 420 MPa or less, 400 MPa or less, or 370 MPa or less. The indentation hardness of the second resin layer 84 is measured by the same method and under the same measurement conditions as the indentation hardness of the upper portion 82C of the resin layer 82.
[0238] (binder resin) The binder resin 84A contains a polymer (cured product) of a polymerizable compound (curable compound). As the polymerizable compound, a polyfunctional (meth)acrylate is preferable. As the polyfunctional (meth)acrylate, the same polyfunctional (meth)acrylate as in the binder resin column of the first resin layer 13 can be used. In addition to the polyfunctional (meth)acrylate, the binder resin may contain a polyfunctional urethane (meth)acrylate, a polyfunctional epoxy (meth)acrylate, and / or a reactive polymer.
[0239] (Inorganic particles) The inorganic particles 84B are the same as the inorganic particles described in the functional layer 31 section.
[0240] <<Functional Layer>> The surface 85A of the functional layer 85 reflects the unevenness of the surface of the resin layer 82. The functional layer 85 may be a single layer, or may have a multi-layer structure of two or more layers. Specifically, the functional layer 85 may have a laminated structure of, for example, an inorganic layer and an anti-soiling layer. By forming the anti-soiling layer, it is possible to prevent fingerprints and the like from adhering.
[0241] (Inorganic layer) The inorganic layer is a layer mainly composed of inorganic matter, and for example, if the inorganic matter is present in the inorganic layer at 55 mass% or more, it corresponds to the inorganic layer. The inorganic layer may contain an organic matter, but is preferably composed only of inorganic matter. Whether or not a layer corresponds to the inorganic layer can be confirmed by X-ray photoelectron spectroscopy (XPS or Electron Spectroscopy for Chemical Analysis: ESCA).
[0242] The constituent materials of the inorganic layer include metals such as Ti, Al, Mg, and Zr, and silicon oxide (SiO x (x=1 to 2)), inorganic oxides such as aluminum oxide, silicon oxynitride, aluminum oxynitride, magnesium oxide, zinc oxide, indium oxide, tin oxide, and yttrium oxide, inorganic nitrides, diamond-like carbon, etc. Among these, silicon oxide is preferable from the viewpoint of improving transmittance and scratch resistance.
[0243] The inorganic layer preferably contains Si atoms. When the inorganic layer contains Si atoms, the refractive index can be reduced. Whether or not the inorganic layer contains Si atoms can be confirmed by X-ray photoelectron spectroscopy (XPS or Electron Spectroscopy for Chemical Analysis (ESCA)).
[0244] The thickness of the inorganic layer is preferably 10 nm or more and 300 nm or less. If the thickness of the inorganic layer is 10 nm or more, excellent scratch resistance can be imparted, and if the thickness is 300 nm or less, the adhesion to other layers is good without affecting the flexibility or optical properties. The lower limit of the thickness of the inorganic layer is more preferably 30 nm or more, 50 nm or more, or 80 nm or more, and the upper limit is more preferably 250 nm or less, 200 nm or less, or 150 nm or less. The thickness of the inorganic layer is determined by the same method as the thickness of the resin layer 82.
[0245] The inorganic layer can be formed by using a deposition method such as a PVD method or a CVD method. Examples of the PVD method include a vacuum deposition method, a sputtering method, and an ion plating method. Examples of the vacuum deposition method include a vacuum deposition method using an electron beam (EB) heating method, and a vacuum deposition method using a high-frequency dielectric heating method.
[0246] (Anti-stain layer) The anti-fouling layer is not particularly limited as long as it has water- and oil-repellency and can impart anti-fouling properties to the obtained optical film 80, but it is preferable that the anti-fouling layer is made of a fluorine-containing organosilicon compound layer obtained by curing a coating of a fluorine-containing organosilicon compound.
[0247] The thickness of the antifouling layer is not particularly limited, but when the antifouling layer is made of a fluorine-containing organosilicon compound layer, the thickness of the antifouling layer is preferably 1 nm or more and 20 nm or less. If the thickness of the antifouling layer is 1 nm or more, the inorganic layer is uniformly covered with the antifouling layer, and the layer is practical in terms of scratch resistance, and if the thickness of the antifouling layer is 20 nm or less, the optical properties such as the haze value of the optical film in the state where the antifouling layer is formed are good. The upper limit of the thickness of the antifouling layer is more preferably 15 nm or less or 10 nm or less.
[0248] The method of forming the fluorine-containing organosilicon compound layer includes a method of applying a composition of a silane coupling agent having a fluoroalkyl group such as a perfluoroalkyl group or a fluoroalkyl group containing a perfluoro(polyoxyalkylene) chain to the surface of an inorganic layer by spin coating, dip coating, casting, slit coating, spray coating, etc., followed by heat treatment, and a vacuum deposition method of vapor-depositing a fluorine-containing organosilicon compound on the surface of an inorganic layer and then heat treatment. In order to obtain a fluorine-containing organosilicon compound layer with high adhesion, it is preferable to form the antifouling layer by a vacuum deposition method. The formation of the fluorine-containing organosilicon compound layer by the vacuum deposition method is preferably carried out using a film-forming composition containing a fluorine-containing hydrolyzable silicon compound.
[0249] The composition for forming a film is not particularly limited as long as it is a composition containing a fluorine-containing hydrolyzable silicon compound and is capable of forming a film by vacuum deposition. The composition for forming a film may contain optional components other than the fluorine-containing hydrolyzable silicon compound, or may be composed only of the fluorine-containing hydrolyzable silicon compound. The optional components include a hydrolyzable silicon compound that does not have a fluorine atom (hereinafter referred to as a "non-fluorine hydrolyzable silicon compound"), a catalyst, etc., which are used within a range that does not impair the effects of the present invention.
[0250] The fluorine-containing hydrolyzable silicon compound used to form the fluorine-containing organosilicon compound coating is not particularly limited, so long as the resulting fluorine-containing organosilicon compound coating has antifouling properties such as water repellency and oil repellency.
[0251] The fluorine-containing hydrolyzable silicon compound can specifically be a fluorine-containing hydrolyzable silicon compound having one or more groups selected from the group consisting of perfluoropolyether group, perfluoroalkylene group and perfluoroalkyl group.These groups exist as fluorine-containing organic groups that are bonded to the silicon atom of hydrolyzable silyl group via a linking group or directly.Note that the perfluoropolyether group refers to a divalent group that has a structure in which perfluoroalkylene group and etheric oxygen atom are bonded alternately.
[0252] Commercially available fluorine-containing organosilicon compounds having one or more groups selected from the group consisting of perfluoropolyether groups, perfluoroalkylene groups, and perfluoroalkyl groups include KP-801, X-71, KY-130, KY-178, KY-185 (all manufactured by Shin-Etsu Chemical Co., Ltd.), Optool (registered trademark) DSX (manufactured by Daikin Industries, Ltd.), etc. Among these, KY-185 and Optool (registered trademark) DSX are preferred.
[0253] In addition, when a commercially available fluorine-containing hydrolyzable silicon compound is supplied together with a solvent, it is preferable to remove the solvent from the commercially available fluorine-containing hydrolyzable silicon compound before use. The above-mentioned film-forming composition is prepared by mixing the fluorine-containing hydrolyzable silicon compound with optional components added as necessary, and is subjected to vacuum deposition.
[0254] The composition for forming a film containing such a fluorine-containing hydrolyzable silicon compound is attached to the surface of an inorganic layer and reacted to form a film, thereby obtaining a fluorine-containing organosilicon compound layer. At this time, the antifouling layer is made of a cured product of the composition for forming a film containing a fluorine-containing hydrolyzable silicon compound. Regarding the specific vacuum deposition method and reaction conditions, conventionally known methods and conditions can be applied.
[0255] <<Other optical films>> 9 includes a functional layer 85, but may not include a functional layer, like an optical film 90 shown in Fig. 11. A surface 90A of the optical film 90 is composed of a surface 82A of a resin layer 82.
[0256] <<<Image display devices>>> The optical films 80 and 90 can be incorporated into a foldable image display device. The structure of the image display device incorporating the optical films 80 and 90 is similar to the structure of the image display device 60, except that the optical films 30 are replaced by the optical films 80 and 90.
[0257] According to this embodiment, since the resin layer 82 contains organic particles 83B, not only the surface 82A of the resin layer 82 but also the surface 80A of the optical film 80 can be made uneven. This makes it possible to blur transmitted and reflected light, so that even if a temporary dent is caused by pressing the surface with a finger, the pressing mark is less noticeable.
[0258] According to this embodiment, the organic particles 83B in the resin layer 82 are unevenly distributed on the resin substrate 81 side from the center line CL, so that pressure is not easily applied to the organic particles 83B near the bent portion S3 during folding, and thus the organic particles 83B are not easily cracked. In particular, if the organic particles in the resin layer are present on the surface side of the resin layer, cracks are likely to occur when the optical film 80 is folded so that the surface of the resin layer faces outward (i.e., when bending outward). However, in this embodiment, the organic particles 83B in the resin layer 82 are unevenly distributed on the resin substrate 81 side from the center line CL, so that cracks can be suppressed even when the optical film 80 is folded so that the surface 82A of the resin layer 82 faces outward. For this reason, such an optical film 80 is particularly effective when the optical film 80 is folded so that the surface 82A of the resin layer 82 faces outward.
[0259] According to this embodiment, the organic particles 83B in the resin layer 82 are unevenly distributed on the resin base material 81 side from the center line CL, so that the organic particles 83B are not present near the surface 82A of the resin layer 82. This can improve the surface hardness and scratch resistance. EXAMPLES
[0260] In order to explain the present invention in detail, examples are given below, but the present invention is not limited to these descriptions.
[0261] <Preparation of composition for hard coat layer> First, the components were mixed so as to obtain the composition shown below, thereby obtaining a composition for a hard coat layer. (Hard Coat Layer Composition 1) Mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (product name "M403", manufactured by Toa Gosei Co., Ltd.): 25 parts by mass Dipentaerythritol EO modified hexaacrylate (product name "A-DPH-6E", manufactured by Shin-Nakamura Chemical Co., Ltd.): 25 parts by weight - Irregularly shaped silica particles (average particle size 25 nm, manufactured by JGC Catalysts and Chemicals Co., Ltd.): 50 parts by weight (based on 100% solids) Polymerization initiator (1-hydroxycyclohexyl phenyl ketone, product name "Omnirad184", manufactured by IGM Resins BV): 4 parts by mass Fluorine-based leveling agent (product name "F568", manufactured by DIC Corporation): 0.2 parts by weight (based on 100% solids) Methyl isobutyl ketone (MIBK): 150 parts by weight
[0262] (Hardcoat layer composition 2) Multifunctional acrylate (product name "KAYARAD PET-30", manufactured by Nippon Kayaku Co., Ltd.): 18 parts by weight EO modified acrylate (product name "ATM-35E", manufactured by Shin-Nakamura Chemical Co., Ltd.): 12 parts by weight Inorganic particles (fumed silica, octylsilane treated, average particle size 12 nm, manufactured by Nippon Aerosil Co., Ltd.): 0.6 parts by mass Organic particles (particle size 2 μm, refractive index 1.555, spherical acrylic-styrene copolymer): 1.5 parts by weight Silicone leveling agent: 0.075 parts by weight Polymerization initiator (product name "Omnirad184", manufactured by IGM Resins BV): 0.3 parts by weight Toluene: 50 parts by weight Propylene glycol monomethyl ether acetate: 17 parts by weight Cyclohexanone: 1 part by weight Isopropanol: 2 parts by weight
[0263] (Hardcoat layer composition 3) EO modified acrylate (product name "A-DPH18E", manufactured by Shin-Nakamura Chemical Co., Ltd.): 15 parts by weight Reactive acrylic polymer (product name "SMP220A", solid content 50%, dilution solvent methyl isobutyl ketone, manufactured by Kyoeisha Chemical Co., Ltd.): 10 parts by weight Inorganic particles (organosilica sol, product name "MIBK-SD", SiO2 solid content 30%, dilution solvent methyl isobutyl ketone, particle size 10 to 15 nm, manufactured by Nissan Chemical Industries, Ltd.): 50 parts by mass Silicone leveling agent: 0.15 parts by weight Polymerization initiator (product name "Omnirad184", manufactured by IGM Resins BV): 1 part by weight Propylene glycol monomethyl ether: 24 parts by weight
[0264] (Hardcoat layer composition 4) Multifunctional acrylate (product name "KAYARAD PET-30", manufactured by Nippon Kayaku Co., Ltd.): 18 parts by weight EO modified acrylate (product name "ATM-35E", manufactured by Shin-Nakamura Chemical Co., Ltd.): 12 parts by weight Organic particles (particle size 3.5 μm, refractive index 1.540, spherical acrylic-styrene copolymer): 2.5 parts by weight Organic particles (particle size 3.5 μm, refractive index 1.555, spherical acrylic-styrene copolymer): 0.4 parts by weight Silicone leveling agent: 0.075 parts by weight Polymerization initiator (product name "Omnirad184", manufactured by IGM Resins BV): 0.3 parts by weight Toluene: 50 parts by weight Propylene glycol monomethyl ether acetate: 18 parts by weight Cyclohexanone: 1 part by weight Isopropanol: 2 parts by weight
[0265] (Hardcoat layer composition 5) Multifunctional acrylate (product name "KAYARAD PET-30", manufactured by Nippon Kayaku Co., Ltd.): 19 parts by weight EO modified acrylate (product name "ATM35E", manufactured by Shin-Nakamura Chemical Co., Ltd.): 16 parts by weight Silicone leveling agent: 0.15 parts by weight Polymerization initiator (product name "Omnirad184", manufactured by IGM Resins BV): 1 part by weight Propylene glycol monomethyl ether: 64 parts by weight
[0266] <Composition for resin layer> The components were mixed so as to obtain the composition shown below, thereby obtaining a composition for a resin layer. (Composition 1 for resin layer) Urethane acrylate (product name "UV3310B", manufactured by Mitsubishi Chemical Corporation): 80 parts by weight Monofunctional acrylic monomer (product name "Viscoat #200", manufactured by Osaka Organic Chemical Industry Co., Ltd.): 20 parts by weight Polymerization initiator (product name "Ominirad127", manufactured by IGM Resins BV): 3 parts by weight Methyl isobutyl ketone (MIBK): 10 parts by weight
[0267] (Composition 2 for resin layer) Urethane acrylate (product name "UV3310B", manufactured by Mitsubishi Chemical Corporation): 80 parts by weight Monofunctional acrylic monomer (product name "Viscoat #150D", manufactured by Osaka Organic Chemical Industry Ltd.): 10 parts by weight Monofunctional acrylic monomer (product name "Viscoat #200", manufactured by Osaka Organic Chemical Industry Ltd.): 10 parts by weight Polymerization initiator (product name "Ominirad127", manufactured by IGM Resins BV): 3 parts by weight Methyl isobutyl ketone (MIBK): 10 parts by weight
[0268] (Composition 3 for resin layer) Urethane acrylate (product name "UV3310B", manufactured by Mitsubishi Chemical Corporation): 80 parts by weight Monofunctional acrylic monomer (product name "Viscoat #150D", manufactured by Osaka Organic Chemical Industry Co., Ltd.): 20 parts by weight Polymerization initiator (product name "Ominirad127", manufactured by IGM Resins BV): 3 parts by weight Methyl isobutyl ketone (MIBK): 10 parts by weight
[0269] (Composition 4 for resin layer) Urethane acrylate (product name "UV3310B", manufactured by Mitsubishi Chemical Corporation): 80 parts by weight Monofunctional acrylic monomer (product name "Viscoat #150D", manufactured by Osaka Organic Chemical Industry Ltd.): 20 parts by weight Polymerization initiator (product name "Ominirad127", manufactured by IGM Resins BV): 1 part by weight Polymerization initiator (product name "Ominirad184", manufactured by IGM Resins BV): 2 parts by weight Methyl isobutyl ketone (MIBK): 10 parts by weight
[0270] (Composition 5 for resin layer) Urethane acrylate (product name "UV3310B", manufactured by Mitsubishi Chemical Corporation): 80 parts by weight Monofunctional acrylic monomer (product name "Viscoat #150D", manufactured by Osaka Organic Chemical Industry Ltd.): 20 parts by weight Polymerization initiator (product name "Ominirad127", manufactured by IGM Resins BV): 6 parts by weight Methyl isobutyl ketone (MIBK): 10 parts by weight
[0271] (Composition for resin layer 6) Urethane acrylate (product name "UV3310B", manufactured by Mitsubishi Chemical Corporation): 80 parts by weight Monofunctional acrylic monomer (product name "ACMO", manufactured by KJ Chemicals Co., Ltd.): 20 parts by weight Polymerization initiator (product name "Ominirad127", manufactured by IGM Resins BV): 3 parts by weight Methyl isobutyl ketone (MIBK): 10 parts by weight
[0272] (Composition for resin layer 7) Urethane acrylate (product name "UV3310B", manufactured by Mitsubishi Chemical Corporation): 80 parts by weight Monofunctional acrylic monomer (product name "IBXA", manufactured by Osaka Organic Chemical Industry Ltd.): 20 parts by weight Polymerization initiator (product name "Ominirad127", manufactured by IGM Resins BV): 3 parts by weight Methyl isobutyl ketone (MIBK): 10 parts by weight
[0273] (Composition 8 for resin layer) Urethane acrylate (product name "UV3310B", manufactured by Mitsubishi Chemical Corporation): 80 parts by weight Monofunctional acrylic monomer (product name "Viscoat #150D", manufactured by Osaka Organic Chemical Industry Ltd.): 10 parts by weight Monofunctional acrylic monomer (product name "Viscoat #200", manufactured by Osaka Organic Chemical Industry Co., Ltd.): 5 parts by weight Monofunctional acrylic monomer (product name "ACMO", manufactured by KJ Chemicals Co., Ltd.): 5 parts by mass Polymerization initiator (product name "Ominirad127", manufactured by IGM Resins BV): 5 parts by weight Methyl isobutyl ketone (MIBK): 10 parts by weight
[0274] (Composition 9 for resin layer) Urethane acrylate (product name "UV3310B", manufactured by Mitsubishi Chemical Corporation): 80 parts by weight Monofunctional acrylic monomer (product name "Viscoat #150D", manufactured by Osaka Organic Chemical Industry Co., Ltd.): 20 parts by weight Polymerization initiator (product name "OminiradTPOH", manufactured by IGM Resins BV): 3 parts by weight Methyl isobutyl ketone (MIBK): 10 parts by weight
[0275] (Composition 10 for resin layer) Urethane acrylate (product name "UV3310B", manufactured by Mitsubishi Chemical Corporation): 80 parts by weight Monofunctional acrylic monomer (product name "Viscoat #150D", manufactured by Osaka Organic Chemical Industry Co., Ltd.): 20 parts by weight Polymerization initiator (product name "Ominirad127", manufactured by IGM Resins BV): 2 parts by weight Polymerization initiator (product name "Ominirad184", manufactured by IGM Resins BV): 2 parts by weight Polymerization initiator (product name "OminiradTPOH", manufactured by IGM Resins BV): 1 part by weight Methyl isobutyl ketone (MIBK): 10 parts by weight
[0276] (Composition 11 for resin layer) Urethane acrylate (product name "UV-3310B", manufactured by Mitsubishi Chemical Corporation): 90 parts by weight Phenoxyethyl acrylate (product name: Viscoat #192, manufactured by Osaka Organic Chemical Industry Co., Ltd.): 10 parts by weight Polymerization initiator (1-hydroxycyclohexyl phenyl ketone, product name "Omnirad184", manufactured by IGM Resins BV): 5 parts by mass Methyl isobutyl ketone: 10 parts by weight
[0277] (Composition 12 for resin layer) Urethane acrylate (product name "UV-3310B", manufactured by Mitsubishi Chemical Corporation): 50 parts by weight Ethoxylated pentaerythritol tetraacrylate (product name "ATM-35E", manufactured by Shin-Nakamura Chemical Co., Ltd.): 40 parts by mass Dicyclopentanyl acrylate (product name "FA-513AS", manufactured by Hitachi Chemical Co., Ltd.): 10 parts by weight Polymerization initiator (1-hydroxycyclohexyl phenyl ketone, product name "Omnirad184", manufactured by IGM Resins BV): 5 parts by mass Methyl isobutyl ketone: 10 parts by weight
[0278] (Composition 13 for resin layer) Urethane acrylate (product name "UV-3310B", manufactured by Mitsubishi Chemical Corporation): 80 parts by weight Ethoxylated pentaerythritol tetraacrylate (product name "ATM-35E", manufactured by Shin-Nakamura Chemical Co., Ltd.): 10 parts by mass Phenoxyethyl acrylate (product name: Viscoat #192, manufactured by Osaka Organic Chemical Industry Co., Ltd.): 10 parts by weight Polymerization initiator (1-hydroxycyclohexyl phenyl ketone, product name "Omnirad184", manufactured by IGM Resins BV): 5 parts by mass Methyl isobutyl ketone: 10 parts by weight
[0279] (Resin layer composition 14) Urethane acrylate (product name "UV-3310B", manufactured by Mitsubishi Chemical Corporation): 80 parts by weight Mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (product name "KAYARAD PET-30", manufactured by Nippon Kayaku Co., Ltd.): 10 parts by mass Phenoxyethyl acrylate (product name: Viscoat #150, manufactured by Osaka Organic Chemical Industry Co., Ltd.): 10 parts by weight Polymerization initiator (1-hydroxycyclohexyl phenyl ketone, product name "Omnirad184", manufactured by IGM Resins BV): 5 parts by mass Methyl isobutyl ketone: 10 parts by weight
[0280] (Composition 15 for resin layer) Urethane acrylate (product name "UV-3310B", manufactured by Mitsubishi Chemical Corporation): 50 parts by weight Ethoxylated pentaerythritol tetraacrylate (product name "ATM-35E", manufactured by Shin-Nakamura Chemical Co., Ltd.): 40 parts by mass Acryloylmorpholine (product name "ACMO", manufactured by KJ Chemicals Co., Ltd.): 10 parts by weight Polymerization initiator (1-hydroxycyclohexyl phenyl ketone, product name "Omnirad184", manufactured by IGM Resins BV): 5 parts by mass Methyl isobutyl ketone: 10 parts by weight
[0281] <Preparation of polyimide substrate composition> First, a 5 L separable flask was charged with a solution of 8,960 g of dehydrated dimethylacetamide and 16.0 g (0.07 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (AprTMOS) dissolved therein, and the solution temperature was controlled at 30°C. Then, 14.6 g (0.03 mol) of 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA) was gradually added so that the temperature did not rise more than 2°C, and the solution was stirred with a mechanical stirrer for 30 minutes. To this was added 400 g (1.25 mol) of 2,2'-bis(trifluoromethyl)benzidine (TFMB). After confirming that it was completely dissolved, 565 g (1.27 mol) of 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA) was gradually added in several portions so that the temperature rise was kept at 2°C or less, thereby synthesizing polyimide precursor solution 1 (solid content 10% by mass) in which polyimide precursor 1 was dissolved.
[0282] <<Example A and Comparative Example A>> <Example A1> A polyethylene terephthalate substrate (product name "Cosmoshine (registered trademark) A4100", manufactured by Toyobo Co., Ltd.) having a thickness of 50 μm was prepared as a release film, and the composition for resin layer 1 was applied to the untreated surface of the polyethylene terephthalate substrate with a bar coater to form a coating film. The formed coating film was then heated at 70° C. for 1 minute to evaporate the solvent in the coating film, and ultraviolet light was irradiated from the coating film side in air using an ultraviolet irradiator (light source H bulb, manufactured by Fusion UV Systems Japan Co., Ltd.) until the accumulated light amount reached 100 mJ / cm. 2 The coating was half-cured by irradiating the light at a rate of 100 nm to form a 50 μm-thick resin layer made of a urethane resin.
[0283] Next, the hard coat layer composition 1 was applied to the surface of the resin layer with a bar coater to form a coating film. The formed coating film was then heated at 70°C for 1 minute to evaporate the solvent in the coating film, and ultraviolet light was irradiated from the coating film side using an ultraviolet irradiator (manufactured by Fusion UV Systems Japan, light source H bulb) under conditions of an oxygen concentration of 200 ppm or less with an accumulated light amount of 300 mJ / cm. 2The coating was completely cured (fully cured) by irradiating the coating with light so as to obtain a hard coat layer having a thickness of 5 μm.
[0284] Thereafter, the resin layer was peeled off from the polyethylene terephthalate substrate, thereby obtaining an optical film consisting of a resin layer made of a urethane-based resin and a hard coat layer.
[0285] The thickness of each layer was measured by photographing the cross section of the optical film using a scanning transmission electron microscope (STEM) (product name "S-4800", manufactured by Hitachi High-Technologies Corporation), measuring the thickness of each layer at 10 points on the image of the cross section, and taking the arithmetic average value of the thicknesses at the 10 points. The cross-sectional photograph of the optical film was taken as follows. First, the optical film cut to 1 mm x 10 mm was embedded in an embedding resin to prepare a block, and a uniform slice with a thickness of 70 nm to 100 nm without holes was cut from this block by a general slice preparation method. An ultramicrotome EM UC7 made by Leica Microsystems was used to prepare the slices. The uniform slice without holes was used as the measurement sample. Then, a cross-sectional photograph of the measurement sample was taken using a scanning transmission electron microscope (STEM). When taking the cross-sectional photograph of the resin layer, SEM observation was performed with the detector set to "SE", the acceleration voltage set to "5 kV", and the emission current set to "10 μA". The magnification was adjusted appropriately from 1000 to 10,000 times while observing whether the layers could be distinguished by adjusting the focus and contrast and brightness. When taking a cross-sectional photograph of the hard coat layer, STEM observation was performed with the detector set to "TE", the acceleration voltage set to "30 kV", and the emission current set to "10 μA". The magnification was adjusted appropriately from 5000 to 200,000 times while observing whether the layers could be distinguished by adjusting the focus and contrast and brightness. In addition, during SEM observation and STEM observation, the beam monitor aperture was set to "3", the objective lens aperture was set to "3", and the WD was set to "8 mm". In Examples A2 to A15 and Comparative Examples A1 and A2, the film thickness of each layer was measured by the same method as in Example A1.
[0286] <Example A2> In Example A2, an optical film was obtained in the same manner as in Example A1, except that the composition 2 for resin layer was used instead of the composition 1 for resin layer.
[0287] <Example A3> In Example A3, an optical film was obtained in the same manner as in Example A1, except that the composition 3 for resin layer was used instead of the composition 1 for resin layer.
[0288] <Example A4> In Example A4, an optical film was obtained in the same manner as in Example A1, except that the composition 4 for resin layer was used instead of the composition 1 for resin layer.
[0289] <Example A5> In Example A5, an optical film was obtained in the same manner as in Example A1, except that the composition 5 for resin layer was used instead of the composition 1 for resin layer.
[0290] <Example A6> In Example A6, an optical film was obtained in the same manner as in Example A1, except that the composition 6 for resin layer was used instead of the composition 1 for resin layer.
[0291] <Example A7> In Example A7, an optical film was obtained in the same manner as in Example A1, except that composition 7 for resin layer was used instead of composition 1 for resin layer.
[0292] <Example A8> In Example A8, an optical film was obtained in the same manner as in Example A3, except that the thickness of the resin layer was 40 μm.
[0293] <Example A9> In Example A9, an optical film was obtained in the same manner as in Example A3, except that the thickness of the resin layer was 25 μm.
[0294] <Example A10> In Example A10, an optical film was obtained in the same manner as in Example A1, except that composition 8 for resin layer was used instead of composition 1 for resin layer, and the thickness of the resin layer was 70 μm.
[0295] <Example A11> In Example A11, an optical film was obtained in the same manner as in Example A10, except that the thickness of the resin layer was 80 μm.
[0296] <Example A12> In Example A12, an optical film was obtained in the same manner as in Example A10, except that the thickness of the resin layer was 90 μm.
[0297] <Example A13> In Example A13, an optical film was obtained in the same manner as in Example A10, except that the thickness of the resin layer was 100 μm.
[0298] <Example A14> In Example A14, an optical film was obtained in the same manner as in Example A10, except that the thickness of the resin layer was 115 μm.
[0299] <Example A15> In Example A15, an optical film was obtained in the same manner as in Example A10, except that the thickness of the resin layer was 140 μm.
[0300] <Comparative Example A1> In Comparative Example A1, instead of the composition for resin layer 1, the composition for resin layer 9 was used, and when forming the resin layer, ultraviolet rays were irradiated from the coating film side in the air with an integrated light amount of 500 mJ / cm 2 2 An optical film was obtained in the same manner as in Example A1, except that irradiation was performed so that the optical film was irradiated in such a manner ...
[0301] <Comparative example A2> In Comparative Example A2, instead of the resin layer composition 1, the resin layer composition 10 was used, and when forming the hard coat layer, ultraviolet rays were additionally irradiated from the release film side in the air with an integrated light amount of 300 mJ / cm 22 An optical film was obtained in the same manner as in Example A1, except that irradiation was performed so that the optical film was irradiated in such a manner ...
[0302] <Displacement measurement> A Berkovich indenter was pressed into the first to third regions of the resin layer of the optical films according to Examples A1 to A15 and Comparative Examples A1 and A2 under a constant load, and the displacements d1 to d3 were measured. Specifically, a block was prepared by embedding an optical film cut to 1 mm×10 mm in an embedding resin, and a uniform slice having a thickness of 70 nm to 100 nm without holes was cut out from the block by a general slice preparation method. An ultramicrotome EM UC7 made by Leica Microsystems was used to prepare the slices. The remaining block from which the uniform slices without holes were cut out was used as a measurement sample. Next, in such a measurement sample, the resin layer was divided into three equal parts in the thickness direction of the resin layer, and the first, second, and third regions were defined in order from the first surface of the resin layer on the hard coat layer side to the second surface on the opposite side to the first surface. Next, in the cross section obtained by cutting out the above-mentioned slice from such a measurement sample, a nanoindenter (TI950 TriboIndenter manufactured by Bruker) was used to vertically indent a Berkovich indenter (triangular pyramid, TI-0039 manufactured by Bruker) as the indenter under the following measurement conditions at the center of the cross section of the first region of the resin layer with a maximum load of 200 μN for 40 seconds, and the displacement (indentation depth) d1 at that time was measured. Here, the Berkovich indenter was indented into a portion of the first region that was 500 nm or more away from each of the two ends of the resin layer toward the center of the resin layer in order to avoid the influence of the side edges of the resin layer. The displacement d1 was taken as the arithmetic average value of the values obtained by measuring at three points. Note that, if the measured values included any value that deviated from the arithmetic average value by ±20% or more, that measured value was excluded and remeasured. Whether or not there was any value that deviated from the arithmetic average value by ±20% or more among the measured values was determined by the formula described in the embodiment. The displacement amount d2 of the second region and the displacement amount d3 of the third region of the resin layer were also measured in the same manner as the displacement amount d1 of the first region. (Measurement conditions) Control method: Load control (maximum load 200μN) Lift amount: 0nm Preload: 0.5μN ·Loading speed: 5μN / sec Maximum load hold time: 5 seconds ·Unloading speed: 5μN / sec ·Temperature: 23℃ Relative humidity: 50%
[0303] <Foldability> A continuous folding test was performed on the optical films according to Examples A1 to A15 and Comparative Examples A1 and A2 to evaluate the foldability. Specifically, first, a sample having a size of 30 mm×100 mm was cut out from the optical film. The two opposing sides of the cut out sample were fixed by the fixing parts of a folding durability tester (product name: U-shaped stretch tester DLDMLH-FS, manufactured by Yuasa System Devices Co., Ltd., compliant with IEC62715-6-1) arranged in parallel. Thereafter, a folding test was performed in which the optical film was folded 100,000 times at 180° under the following conditions so that the minimum interval φ between the two opposing sides was 10 mm and the front side (hard coat layer side) of the optical film was on the outside as shown in FIG. 4(C), and the bending part was checked for deformation, cracks, or breakage. The continuous folding test was performed under an environment of a temperature of 23° C. and a relative humidity of 50%. The evaluation criteria were as follows. The folding property was deemed to be good as long as no cracks or breaks occurred at the bent portions. A: During the continuous folding test, no deformation, cracks or breaks occurred in the bent parts. B: In the continuous folding test, deformation at the bent portion was confirmed to a level that did not cause practical problems, but no cracks or breaks occurred. C: In the continuous folding test, deformation was clearly observed at the bent portion, but no cracks or breaks occurred. D: During the continuous folding test, cracks or breaks occurred at the bent portion.
[0304] <Impact resistance> Impact resistance tests were performed using the optical films according to Examples A1 to A15 and Comparative Examples A1 and A2. Specifically, the optical films according to Examples A1 to A15 and Comparative Examples A1 and A2 were placed directly on the surface of a 0.7 mm thick soda glass with the hard coat layer facing up, and an iron ball weighing 100 g and having a diameter of 30 mm was dropped from a height of 30 cm onto the surface of the hard coat layer of the optical film, three times each. In the impact resistance test, the position where the iron ball was dropped was changed each time. Then, the optical film after the impact resistance test was visually evaluated for whether the surface of the hard coat layer was dented or the soda glass was cracked. The evaluation results were as follows. In addition, the impact resistance was considered to be good unless either the dent evaluation of the surface of the hard coat layer or the crack evaluation of the soda glass was "D". (Evaluation of dents on the surface of the hard coat layer) A: When the hard coat layer was observed from the front and from an oblique direction, no depressions were found on the surface of the hard coat layer. B: When the hard coat layer was observed either from the front or from an oblique direction, depressions were found on the surface of the hard coat layer, but were not of a level that would cause practical problems. C: When the hard coat layer was observed from the front, no dents were observed on the surface of the hard coat layer, but when observed obliquely, dents were confirmed on the surface of the hard coat layer. D: When the hard coat layer was observed from the front and from an oblique angle, obvious depressions were observed on the surface of the hard coat layer. (Soda glass cracking evaluation) A: The soda glass did not break or get scratched. B: The soda glass was scratched but did not break. C: The soda glass cracked once. D: The soda glass cracked two or three times.
[0305] <Pencil hardness> The pencil hardness of the surface (surface of the hard coat layer) of the optical film according to Examples A1 to A15 and Comparative Examples A1 and A2 was measured based on JIS K5600-5-4:1999. Specifically, the optical film cut to a size of 30 mm×100 mm was fixed on a glass plate of 50 mm×100 mm with a thickness of 2 mm with cellophane tape (registered trademark) manufactured by Nichiban Co., Ltd. so as not to be folded or wrinkled. Then, using a pencil hardness tester (product name "Pencil Scratch Coating Hardness Tester (Electric)" manufactured by Toyo Seiki Seisakusho Co., Ltd.), a pencil (product name "Uni", manufactured by Mitsubishi Pencil Co., Ltd.) was moved at a speed of 1 mm / sec under an environment of a temperature of 23° C. and a relative humidity of 50% while applying a load of 750 g to the pencil. The pencil hardness was determined as the highest hardness at which the surface of the optical film (surface of the hard coat layer) was not scratched in the pencil hardness test. When measuring the pencil hardness, multiple pencils with different hardnesses were used. The pencil hardness test was performed five times for each pencil. If no scratches were visible on the surface of the optical film when the surface was observed through a fluorescent light four or more times out of the five, it was determined that the pencil of that hardness did not scratch the surface of the optical film.
[0306] The results are shown in Table 1 below. [Table 1]
[0307] The results are described below. The optical film according to Comparative Example A1 had poor foldability because the displacement amount d1 was larger than the displacement amount d2 and did not satisfy the above relational formula (1). The optical film according to Comparative Example A2 had poor foldability because the displacement amount d2 was larger than the displacement amount d3 and did not satisfy the above relational formula (1). In contrast, the optical films according to Examples A1 to A15 had good foldability and impact resistance because they satisfied the above relational formula (1).
[0308] <<Example B and Comparative Example B>> <Example B1> Using the polyimide precursor solution 1 obtained above, a single-layer polyimide substrate having a thickness of 12 μm was produced by the following procedure. First, the polyimide precursor solution 1 was applied onto a glass plate and dried in a circulation oven at 120° C. for 10 minutes to form a coating film. After forming the coating film, the glass plate with the coating film was heated to 350° C. at a heating rate of 10° C. / min under a nitrogen stream (oxygen concentration 100 ppm or less), held at 350° C. for 1 hour, and then cooled to room temperature. As a result, a single-layer polyimide substrate formed on the glass plate was obtained.
[0309] Next, the composition 1 for hard coat layer was applied to the surface (second surface) of the polyimide substrate with a bar coater to form a coating film. The formed coating film was then heated at 70°C for 1 minute to evaporate the solvent in the coating film, and ultraviolet rays were irradiated in air with an integrated light amount of 200 mJ / cm using an ultraviolet irradiation device (manufactured by Fusion UV Systems Japan, light source H bulb). 2 The coating was cured by irradiating the polyimide substrate with light so as to obtain a hard coat layer having a thickness of 5 μm.
[0310] After forming a hard coat layer on the polyimide substrate, the glass plate was peeled off from the polyimide substrate, and the resin layer composition 11 was applied to the first surface of the polyimide substrate opposite to the second surface with a bar coater to form a coating film. The formed coating film was then heated at 70°C for 1 minute to evaporate the solvent in the coating film, and ultraviolet light was irradiated in air with an ultraviolet ray irradiation device (manufactured by Fusion UV Systems Japan, light source H bulb) at an integrated light amount of 1200 mJ / cm. 2 The coating was cured by irradiating the coating with light so as to form a resin layer made of a urethane resin having a thickness of 80 μm, thereby obtaining an optical film.
[0311] The thickness of the polyimide substrate was measured by photographing the cross section of the polyimide substrate using a scanning electron microscope (SEM), measuring the thickness of the polyimide substrate at 20 points on the image of the cross section, and taking the arithmetic average value of the thicknesses at the 20 points. The method of photographing the cross section was the same as the method of photographing the cross section when measuring the film thickness of the hard coat layer described in the column of Example A. The film thickness of the resin layer and the film thickness of the hard coat layer were also measured by the same method as the thickness of the polyimide substrate. In other Examples B2 to B7 and Comparative Examples B1 to B4, the thickness of the polyimide substrate, the film thickness of the resin layer, and the film thickness of the hard coat layer were also measured by the same method as in Example B1.
[0312] <Example B2> In Example B2, an optical film was obtained in the same manner as in Example B1, except that the thickness of the polyimide substrate was 8 μm.
[0313] <Example B3> In Example B3, an optical film was obtained in the same manner as in Example B1, except that the thickness of the polyimide substrate was 18 μm.
[0314] <Example B4> In Example B4, an optical film was obtained in the same manner as in Example B1, except that the thickness of the resin layer was 60 μm.
[0315] <Example B5> In Example B5, an optical film was obtained in the same manner as in Example B1, except that the thickness of the resin layer was 100 μm.
[0316] <Example B6> In Example B6, an optical film was obtained in the same manner as in Example B1, except that the composition 12 for resin layer was used instead of the composition 11 for resin layer.
[0317] <Example B7> In Example B7, an optical film was obtained in the same manner as in Example B1, except that the composition 13 for resin layer was used instead of the composition 11 for resin layer.
[0318] <Comparative Example B1> In Comparative Example B1, an optical film was obtained in the same manner as in Example B1, except that the thickness of the polyimide substrate was 30 μm.
[0319] <Comparative example B2> In Comparative Example B2, an optical film was obtained in the same manner as in Example B1, except that the thickness of the resin layer was 30 μm.
[0320] <Comparative Example B3> In Comparative Example B3, an optical film was obtained in the same manner as in Example B1, except that the composition 14 for resin layer was used instead of the composition 11 for resin layer.
[0321] <Comparative example B4> In Comparative Example B4, an optical film was obtained in the same manner as in Example B1, except that the composition 15 for resin layer was used instead of the composition 11 for resin layer.
[0322] <Displacement measurement> A Berkovich indenter was pressed into the cross section of the polyimide substrate and the resin layer of the optical films according to Examples B1 to B7 and Comparative Examples B1 to B4 with a maximum load of 200 μN, and the displacement d4 of the polyimide substrate and the displacement d5 of the resin layer were measured. The displacement d4 was measured by the same method as the measurement method for the displacements d1 to d3 described in the column of Example A. However, in order to avoid the influence of the side edges of the polyimide substrate, the Berkovich indenter was pressed into a portion 500 nm or more away from each of the two ends of the polyimide substrate toward the center of the polyimide substrate. The displacement d4 was taken as the arithmetic average value of the values obtained by measuring at three points. Note that, if any of the measured values deviated from the arithmetic average value by ±20% or more, that measured value was excluded and remeasured. Whether or not any of the measured values deviated from the arithmetic average value by ±20% or more was determined by the formula described in the embodiment. The displacement d5 of the resin layer was also measured in the same manner as the displacement d4 of the polyimide substrate.
[0323] <Foldability> A continuous folding test was carried out on the optical films according to Examples B1 to B7 and Comparative Examples B1 to B4 to evaluate the foldability. The continuous folding test was carried out in the same manner as the continuous folding test described in the column of Example A. The evaluation criteria were also the same as those of the continuous folding test described in the column of Example A.
[0324] <Folding Habit Evaluation> In the optical films according to Examples B1 to B7 and Comparative Examples B1 to B4, whether or not a folding crease was observed when a folding static test was performed was evaluated. Specifically, first, an optical film cut to a size of 30 mm×100 mm was obtained. Then, a region of 30 mm×48 mm including two opposing short sides (30 mm) of the cut optical film was fixed to a glass plate of a size of 50 mm×100 mm. The glass plate was fixed to the resin layer side of the optical film. Then, the glass plate was arranged parallel to the opposing sides of the optical film so that the distance between the sides was 2.5 mm, and the optical film was folded so that the hard coat layer was on the inside. In this state, a folding static test was performed in which the film was left at a temperature of 25° C. and a relative humidity of 50% for 100 hours. Then, the optical film was opened with the glass plate attached, and the surface of the optical film was flattened. Then, it was confirmed whether or not a folding crease was observed on the surface of the optical film. The evaluation criteria were as follows. A: No creases were found in the optical film when observed from the front and obliquely. B: When the optical film was observed from the front or obliquely, some folding creases were found in the optical film, but were at a level that would not cause any practical problems. C: When the optical film was observed from the front, no fold was observed in the optical film, but when observed obliquely, a fold was confirmed in the optical film. D: When the optical film was observed from the front and obliquely, a clear crease was observed in the optical film.
[0325] <Impact resistance evaluation> Impact resistance tests were performed using the optical films according to Examples B1 to B7 and Comparative Examples B1 to B4. Specifically, first, an optical film was cut into a size of 50 mm x 50 mm. Then, the optical film was directly placed on the surface of a soda glass of 50 mm x 50 mm with a thickness of 0.7 mm, with the hard coat layer side facing up, and an impact resistance test was performed three times for each case in which a ballpoint pen (orange 0.7 manufactured by BIC Japan) weighing 100 g and having a nib with a diameter of 0.7 mm was dropped from a position of 30 cm above the surface of the hard coat layer of the optical film with the nib facing downward. In the impact resistance test, the position where the pen was dropped was changed each time. Then, in the optical film after the impact resistance test, whether the surface of the hard coat layer was recessed was visually evaluated. The evaluation results were as follows. A: When the hard coat layer was observed from the front and from an oblique direction, no depressions were found on the surface of the hard coat layer. B: When the hard coat layer was observed either from the front or from an oblique direction, depressions were found on the surface of the hard coat layer, but were not of a level that would cause practical problems. C: When the hard coat layer was observed from the front, no dents were observed on the surface of the hard coat layer, but when observed obliquely, dents were confirmed on the surface of the hard coat layer. D: When the hard coat layer was observed from the front and from an oblique angle, obvious depressions were observed on the surface of the hard coat layer.
[0326] <Pencil hardness> The pencil hardness of the surface (surface of the hard coat layer) of the optical films according to Examples B1 to B7 and Comparative Examples B1 to B4 was measured based on JIS K5600-5-4: 1999. The pencil hardness was measured by the same method as that described in the column for Example A.
[0327] The results are shown in Table 2 below. [Table 2]
[0328] The results are described below. In the optical film according to Comparative Example B1, the thickness of the polyimide substrate was too thick, so a folding habit was confirmed after the folding static test. In the optical film according to Comparative Example B2, the thickness of the resin layer was too thin, so good impact resistance was not obtained. In the optical film according to Comparative Example B3, the displacement amount of the resin layer due to the indentation test was too small, so good foldability was not obtained. In the optical film according to Comparative Example B4, the displacement amount of the resin layer due to the indentation test was too large, so impact resistance could not be ensured. In contrast, in the optical films of Examples B1 to B7, the thickness of the polyimide substrate was 20 μm or less, the thickness of the resin layer was 50 μm or more, the ratio of the thickness of the resin layer to the thickness of the polyimide substrate was 4.0 or more and 12.0 or more, the displacement amount d4 of the polyimide substrate when the indentation test was performed was 50 nm or more and 250 nm or less, and the displacement amount d5 of the resin layer when the indentation test was performed was 200 nm or more and 1500 nm or less. Therefore, no folding creases were observed when the folding static test was performed, and good impact resistance was obtained.
[0329] <<Example C and Comparative Example C>> <Example C1> A polyimide-based substrate (product name "Neoprim (registered trademark)", manufactured by Mitsubishi Gas Chemical Company, Inc.) having a thickness of 50 μm was prepared as the resin substrate. The Neoprim (registered trademark) used in Examples C1 to C5 and Comparative Examples C1 to C3 was commercially available as a polyimide film. Then, the composition 2 for hard coat layer was applied to one surface of the polyimide-based substrate using a bar coater to form a coating film. Thereafter, the formed coating film was heated at 70°C for 1 minute to evaporate the solvent in the coating film, and ultraviolet rays were irradiated in air using an ultraviolet irradiation device (light source H bulb, manufactured by Fusion UV Systems Japan Co., Ltd.) until the accumulated light amount reached 200 mJ / cm. 2 The coating was cured by irradiating the coating with light so as to form a first hard coat layer having a thickness of 3 μm.
[0330] Next, the composition 3 for hard coat layer was applied to the surface of the first hard coat layer with a bar coater to form a coating film. The formed coating film was heated at 70°C for 1 minute to evaporate the solvent in the coating film, and ultraviolet rays were irradiated using an ultraviolet irradiator (manufactured by Fusion UV Systems Japan, light source H bulb) under conditions of an oxygen concentration of 200 ppm or less with an accumulated light amount of 200 mJ / cm. 2 The coating was cured by irradiating the coating with light so that the cured coating was cured. As a result, a hard coat layer was formed on the polyimide substrate, which was composed of a first hard coat layer having a thickness of 3 μm and a second hard coat layer having a thickness of 3 μm laminated on the first hard coat layer, to obtain an optical film.
[0331] The thickness of each layer was measured by photographing the cross section of the optical film using a scanning transmission electron microscope (STEM) (product name "S-4800", manufactured by Hitachi High-Technologies Corporation), measuring the thickness of each layer at 10 points on the image of the cross section, and taking the arithmetic average value of the thicknesses at the 10 points. The cross-sectional photograph of the optical film was taken as follows. First, the optical film cut to 1 mm x 10 mm was embedded in an embedding resin to prepare a block, and a uniform slice with a thickness of 70 nm to 100 nm without holes was cut out from this block by a general slice preparation method. An ultramicrotome EM UC7 made by Leica Microsystems was used to prepare the slice. The uniform slice without holes was used as the measurement sample. Then, a cross-sectional photograph of the measurement sample was taken using a scanning transmission electron microscope (STEM). When taking this cross-sectional photograph, STEM observation was performed with the detector set to "TE", the acceleration voltage set to "30 kV", and the emission current set to "10 μA". The magnification was adjusted appropriately from 5,000 to 200,000 times while adjusting the focus and observing whether the contrast and brightness of each layer could be distinguished. When taking the cross-sectional photograph, the beam monitor aperture was set to "3", the objective lens aperture was set to "3", and the WD was set to "8 mm". In Examples C2 to C5 and Comparative Examples C1 to C3, the film thickness of each layer was measured by the same method as in Example C1.
[0332] <Example C2> In Example C2, an optical film was obtained in the same manner as in Example C1, except that the thickness of the first hard coat layer was 4 μm and the thickness of the second hard coat layer was 4 μm.
[0333] <Example C3> In Example C3, an optical film was obtained in the same manner as in Example C1, except that the composition 4 for a hard coat layer was used instead of the composition 2 for a hard coat layer.
[0334] <Example C4> In Example C4, an optical film was obtained in the same manner as in Example C1, except that the composition 5 for a hard coat layer was used instead of the composition 3 for a hard coat layer. <Example C5> In Example C5, a SiO film having a thickness of 100 nm was formed on the surface of the second hard coat layer of the optical film according to Example C1 by a sputtering method. x An optical film was obtained in the same manner as in Example C1, except that an inorganic layer made of (x=1 to less than 2) was formed, and then an antifouling layer made of a fluorine-containing organosilicon compound and having a thickness of 2 nm was formed by vacuum deposition.
[0335] <Comparative Example C1> A polyimide-based substrate (product name "Neoprim (registered trademark)" manufactured by Mitsubishi Gas Chemical Company, Inc.) having a thickness of 50 μm was prepared as a resin substrate, and the composition 2 for hard coat layer was applied to the first surface, which was one surface of the polyimide-based substrate, using a bar coater to form a coating film. The formed coating film was then heated at 70°C for 1 minute to evaporate the solvent in the coating film, and ultraviolet rays were irradiated using an ultraviolet irradiation device (manufactured by Fusion UV Systems Japan, light source H bulb) at an oxygen concentration of 200 ppm or less and an accumulated light amount of 400 mJ / cm. 2 The coating was cured by irradiating the light so as to form a hard coat layer having a thickness of 6 μm, thereby obtaining an optical film.
[0336] <Comparative Example C2> In Comparative Example C2, an optical film was obtained in the same manner as in Example C1, except that the composition 3 for hard coat layer was used instead of the composition 2 for hard coat layer, and the composition 2 for hard coat layer was used instead of the composition 3 for hard coat layer. That is, the optical film according to Comparative Example C2 had a second hard coat layer containing organic particles on the first hard coat layer.
[0337] <Comparative Example C3> A polyimide-based substrate (product name "Neoprim (registered trademark)", manufactured by Mitsubishi Gas Chemical Company, Inc.) having a thickness of 50 μm was prepared as the resin substrate, and the composition 3 for hard coat layer was applied to the first surface, which was one surface of the polyimide-based substrate, using a bar coater to form a coating film. Thereafter, the formed coating film was heated at 70°C for 1 minute to evaporate the solvent in the coating film, and ultraviolet rays were irradiated in air using an ultraviolet irradiation device (manufactured by Fusion UV Systems Japan, light source H bulb) to an accumulated light amount of 200 mJ / cm. 2 The coating was cured by irradiating the light so as to form a hard coat layer having a thickness of 6 μm, thereby obtaining an optical film.
[0338] <Evaluation of uneven distribution of organic particles> In the optical films according to Examples C1 to C5 and Comparative Examples C1 and C2, it was examined whether the organic particles were unevenly distributed on the polyimide-based substrate side from the center line that divides the hard coat layer in the thickness direction of the hard coat layer. Specifically, first, a scanning transmission electron microscope (STEM) (product name "S-4800", manufactured by Hitachi High-Technologies Corporation) was used to photograph the cross section of the hard coat layer under the same conditions as those for measuring the thickness of each layer, and 10 cross-sectional photographs were prepared. In each cross-sectional photograph, the thickness of the hard coat layer was measured, and the center line was obtained in each cross-sectional photograph. In addition, the center of the organic particles appearing in each cross-sectional photograph was obtained. The center was obtained by determining the midpoint of a virtual line segment connecting the closest point and the farthest point of the organic particles to the polyimide-based substrate in the thickness direction of the hard coat layer. Then, the distance between the center of the organic particles and the center line was measured in each cross-sectional photograph. In this case, the distance between the center of the organic particle and the center line was marked "-" when the center of the organic particle was located below the center line (on the polyimide substrate side), and the distance between the center of the organic particle and the center line was marked "+" when the center of the organic particle was located above the center line. The average position of the centers was determined by averaging the distances, and whether the average position was "-" or "+" was used to determine whether the particles were present on the polyimide substrate side of the center line. The evaluation criteria were as follows. The optical film of Comparative Example C3 did not contain organic particles, and was therefore not included in this evaluation. A: The organic particles were unevenly distributed on the polyimide substrate side from the center line. B: The organic particles were not unevenly distributed on the polyimide substrate side from the center line.
[0339] <Foldability> A continuous folding test was performed on the optical films according to Examples C1 to C5 and Comparative Examples C1 to C3 to evaluate the foldability. Specifically, first, the optical film cut into a size of 30 mm x 100 mm was attached to a durability tester (product name "DLDMLH-FS", manufactured by Yuasa System Equipment Co., Ltd.) with the short sides of the optical film fixed at the fixing parts, and the minimum distance between the two opposing sides was 8 mm as shown in FIG. 4(C). A folding test was performed 100,000 times to fold the optical film 180° so that the front side (the hard coat layer side in Examples C1 to C4 and Comparative Examples C1 to C3 and the antifouling layer side in Example C5) was on the outside, and it was checked whether cracks or breaks occurred in the bent parts. The evaluation criteria were as follows. A: During the continuous folding test, no cracks or breaks occurred at the bent parts. B: In the continuous folding test, some cracks were observed at the bent portion, but the level was not significant enough to cause any problems in practical use. C: During the continuous folding test, cracks or breaks were clearly observed at the bent portions.
[0340] <Haze value measurement> For the optical films according to Examples C1 to C5 and Comparative Examples C1 to C3, the haze value (total haze value) was measured in accordance with JIS K7136:2000 using a haze meter (product name "HM-150", manufactured by Murakami Color Research Laboratory Co., Ltd.) under an environment of a temperature of 23°C and a relative humidity of 50%. The total light transmittance and the haze value were measured three times for each optical film by cutting out an optical film into a size of 50 mm x 100 mm, placing the optical film in the haze meter without curls or wrinkles and without fingerprints or dust, with the polyimide-based substrate side facing the light source, and taking the arithmetic average value of the values obtained by the three measurements.
[0341] <Transmitted image clarity> For the optical films according to Examples C1 to C5 and Comparative Examples C1 to C3, the transmitted image clarity was measured in an environment of a temperature of 23° C. and a relative humidity of 50% or less using an image clarity measuring device (product name "ICM-1T", manufactured by Suga Test Instruments Co., Ltd.) according to JIS K7374:2007. The transmitted image clarity was measured by cutting an optical film into a size of 50 mm×100 mm, without curls or wrinkles, and without fingerprints or dust, and placing the optical axis rotating table and sample stage in the image clarity measuring device set to "transmission" so that the polyimide substrate side was the light source side, measuring three times for one optical comb, and taking the arithmetic average value of the values obtained by the three measurements.
[0342] <Evaluation of pressure marks> The optical films according to Examples C1 to C5 and Comparative Examples C1 to C3 were subjected to appearance observation under an environment of a temperature of 23°C and a relative humidity of 50% or less. Specifically, a colorless transparent glass having a thickness of 1 mm was bonded to the polyimide-based substrate side of the optical film via two transparent adhesive layers having a thickness of 100 μm (product number "8146-4", manufactured by 3M Co.) to prepare an evaluation sample having a size of 5 cm x 10 cm. Then, the optical film was placed on a black table with the optical film facing up. Next, a polyethylene terephthalate film (PET film) having a thickness of 250 μm and a size of 20 mm x 200 mm (product name "A4300", Toyobo Co., Ltd.) was placed on the evaluation sample, and a cylindrical weight of 300 g having a diameter of 35 mm was placed on the PET film. After leaving it for 1 minute, the weight and the PET film were removed. Then, after 3 seconds, it was observed whether the PET film had a pressing mark of the weight. The evaluation criteria were as follows. (Indentation evaluation) A: No pressure marks were found. B: A small amount of pressure marks were observed, but the level was not problematic for practical use. C: Pressure marks were clearly observed.
[0343] <Indentation hardness (H IT ) Measurement> The indentation hardness (H IT) were measured. Specifically, first, a block was prepared by embedding an optical film cut to 1 mm×10 mm in an embedding resin, and a uniform slice having a thickness of 70 nm to 100 nm without holes was cut from this block by a general slice preparation method. An ultramicrotome EM UC7 made by Leica Microsystems was used to prepare the slices. The remaining block from which the uniform slice without holes was cut was used as a measurement sample. Next, a Berkovich indenter (triangular pyramid, TI-0039 made by BRUKER) was pressed vertically into the lower cross section of the hard coat layer for 10 seconds up to a maximum pressing load of 50 μN using a TI950 TriboIndenter made by BRUKER under the following measurement conditions in the cross section obtained by cutting out the slice in such a measurement sample. Here, the Berkovich indenter was pressed into the lower part of the hard coat layer at a distance of 500 nm from the interface between the polyimide substrate and the hard coat layer toward the center of the hard coat layer, and at least 500 nm from each of the two ends of the hard coat layer toward the center of the hard coat layer. After that, the load was removed over a period of 10 seconds after the above-mentioned maximum pressing load P max and the contact projection area A p Using and, P max / A p The indentation hardness (H IT The above contact projected area is the contact projected area corrected for the indenter tip curvature by the Oliver-Pharr method using a standard sample of fused quartz (5-0098 manufactured by BRUKER). Indentation hardness (H IT) was the arithmetic average value of the values obtained by measuring at 10 points. If the measured values included values that deviated from the arithmetic average value by ±20% or more, those measured values were excluded and remeasured. Whether or not there were any measured values that deviated from the arithmetic average value by ±20% or more was determined by whether the value (%) calculated by (AB) / B×100, where the measured value is A and the arithmetic average value is B, was ±20% or more. The indentation hardness of the upper part of the hard coat layer was measured in the same manner as the indentation hardness of the lower part of the hard coat layer, but in this case, the Berkovich indenter was pressed into a part of the upper part of the hard coat layer that was 500 nm away from the surface of the hard coat layer toward the center of the hard coat layer and 500 nm or more away from each of the both ends of the hard coat layer toward the center of the hard coat layer. (Measurement conditions) Control method: Load control method ·Loading speed: 5μN / sec ·Holding time: 5 seconds ·Loading and unloading speed: 5μN / sec ·Temperature: 23℃ Relative humidity: 50%
[0344] <Scratch resistance> The surfaces of the optical films according to Examples C1 to C5 were subjected to a scratch resistance test and evaluated. Specifically, the optical films cut into pieces measuring 50 mm x 100 mm were fixed on a glass plate with Cellotape (registered trademark) manufactured by Nichiban Co., Ltd. so that the surfaces of the optical films faced up without bending or wrinkling. In this state, the optical films were fixed on a glass plate with a thickness of 1 kgf / cm using steel wool with a no. 0000 rating (product name "BON STAR", manufactured by Nippon Steel Wool Co., Ltd.). 2 The glass was rubbed 10 times back and forth at a speed of 60 mm / sec under an environment of a temperature of 23°C and a relative humidity of 50% while applying a load of 100 g / s. After that, black vinyl tape (black vinyl tape No. 200-38-21 manufactured by Yamato Co., Ltd.) was applied to the glass surface opposite to the surface on which the optical film was applied, and the presence or absence of scratches was visually confirmed under a three-wavelength fluorescent lamp. The evaluation criteria were as follows. A: No injuries were found. B: A few scratches were observed, but were not of a level that would cause any practical problems. C: More scratches than ○ were found. D: Numerous scratches were found.
[0345] The results are shown in Tables 3 and 4 below. [Table 3]
[0346] [Table 4]
[0347] The results are described below. The optical films according to Comparative Examples C1 and C2 had poor continuous folding properties because the organic particles were not unevenly distributed on the polyimide-based substrate side from the center line. This is believed to be because cracks were generated from the interface between the organic particles and the binder resin near the surface of the hard coat layer at the bent portion of the optical film during the continuous folding test, causing the film to break. In addition, the optical film according to Comparative Example C3 had a hard coat layer that did not contain organic particles, so the pressure marks of the weight were clearly confirmed. This is believed to be because the surface of the hard coat layer was a flat surface. In contrast, the optical films according to Examples C1 to C5 had excellent continuous folding properties and the pressure marks were not noticeable because the organic particles were unevenly distributed on the polyimide-based substrate side from the center line. [Explanation of symbols]
[0348] 10, 72, 82...Resin layer 30, 50, 70, 80...Optical film 31, 52, 85…Functional layers 51, 71, 81...Resin substrate 60...Image display device 62...Display element 73...Hard coat layer
Claims
1. An optical film having a foldable laminated structure for use in an image display device, the optical film having a light-transmitting resin layer and a functional layer, the resin layer has a first surface in contact with the functional layer and a second surface opposite to the first surface, The functional layer is a hard coat layer, an optical film in which the resin layer is divided into three equal parts in a thickness direction of the resin layer, which are successively divided into a first region, a second region, and a third region from the first surface to the second surface of the resin layer, and an indentation test is performed in which a Berkovich indenter is pressed with a constant load into each of the first region, the second region, and the third region in a cross section of the resin layer in the thickness direction, where the displacement amount in the first region is d1, the displacement amount in the second region is d2, and the displacement amount in the third region is d3, satisfying the relationship d1<d2<d3.
2. 2. The optical film of claim 1, wherein the ratio of d1 to d3 is less than or equal to 0.
85.
3. 3. The optical film according to claim 1, wherein d1 to d3 are each 200 nm or more and 1000 nm or less.
4. 4. The optical film according to claim 1, having a thickness of 20 μm or more and 150 μm or less.
5. The optical film according to claim 1 , further comprising a resin substrate provided on one of the first surface and the second surface of the resin layer.
6. A foldable optical film for use in an image display device, comprising: A resin substrate; A resin layer provided on one surface side of the resin substrate and containing organic particles, the surface of the resin layer is an uneven surface, the organic particles are unevenly distributed on the resin substrate side relative to a center line that bisects the resin layer in a thickness direction of the resin layer, An optical film, wherein the indentation hardness of a lower portion of the resin layer located on the resin substrate side is smaller than the indentation hardness of an upper portion of the resin layer located on the surface side.
7. The optical film according to claim 6 , wherein the resin substrate comprises one or more resins selected from the group consisting of polyimide-based resins, polyamideimide-based resins, polyamide-based resins, and polyester-based resins.
8. The optical film according to claim 6 or 7, wherein the resin layer has a thickness of 2 μm or more and 15 μm or less.
9. 9. The optical film according to claim 6, wherein the resin layer comprises a first resin layer and a second resin layer provided on the surface side of the first resin layer, and the first resin layer contains the organic particles.
10. 10. The optical film according to claim 1, wherein the optical film does not crack or break when a test of folding the optical film 180° so that the distance between opposing sides of the optical film is 10 mm is repeated 100,000 times.
11. A display element; The optical film according to claim 1 , which is disposed on a viewer side relative to the display element; An image display device comprising:
12. The image display device according to claim 11 , wherein the display element is an organic light-emitting diode element.
Citation Information
Patent Citations
Particle dispersed resin sheet, substrate for image display apparatus, and image display apparatus
JP2004264564A
Hard coat film
JP2009042647A
Optical film
JP2011083955A
Window film for display device, and display device including the same
JP2016125063A
Optical laminate
JP2016132187A